Transporters and mechanisms of hormone transport in arabidopsis - Abualia, Rashed; Benková, Eva; Lacombe, Benoît (Advances in Botanical Research)
Plant hormones as signalling molecules play an essential role in the control of plant growth and development. Typically, sites of hormonal action are usually distant from the site of biosynthesis thus relying on efficient transport mechanisms. Over the last decades, molecular identification of proteins and protein complexes involved in hormonal transport has started. Advanced screens for genes involved in hormonal transport in combination with transport assays using heterologous systems such as yeast, insect, or tobacco BY2 cells or Xenopus oocytes provided important insights into mechanisms underlying distribution of hormones in plant body and led to identification of principal transporters for each hormone. This review gives a short overview of the mechanisms of hormonal transport and transporters identified in Arabidopsis thaliana.

Chemokines and integrins independently tune actin flow and substrate friction during intranodal migration of T cells - Hons, Miroslav; Kopf, Aglaja; Hauschild, Robert; Leithner, Alexander F; Gärtner, Florian R; Abe, Jun; Renkawitz, Jörg; Stein, Jens; Sixt, Michael K (Nature Immunology)
Although much is known about the physiological framework of T cell motility, and numerous rate-limiting molecules have been identified through loss-of-function approaches, an integrated functional concept of T cell motility is lacking. Here, we used in vivo precision morphometry together with analysis of cytoskeletal dynamics in vitro to deconstruct the basic mechanisms of T cell migration within lymphatic organs. We show that the contributions of the integrin LFA-1 and the chemokine receptor CCR7 are complementary rather than positioned in a linear pathway, as they are during leukocyte extravasation from the blood vasculature. Our data demonstrate that CCR7 controls cortical actin flows, whereas integrins mediate substrate friction that is sufficient to drive locomotion in the absence of considerable surface adhesions and plasma membrane flux.

Incorrect trafficking route leads to autism - Contreras, Ximena; Hippenmeyer, Simon (Brain a journal of neurology)
This scientific commentary refers to ‘NEGR1 and FGFR2 cooperatively regulate cortical development and core behaviours related to autism disorders in mice’ by Szczurkowska et al.

Real-time analysis of auxin response, cell wall pH and elongation in Arabidopsis thaliana Hypocotyls - Li, Lanxin; Krens, Gabriel; Fendrych, Matyas; Friml, Jirí (Bio-protocol)
The rapid auxin-triggered growth of the Arabidopsis hypocotyls involves the nuclear TIR1/AFB-Aux/IAA signaling and is accompanied by acidification of the apoplast and cell walls (Fendrych et al., 2016). Here, we describe in detail the method for analysis of the elongation and the TIR1/AFB-Aux/IAA-dependent auxin response in hypocotyl segments as well as the determination of relative values of the cell wall pH.

Haploinsufficiency of the intellectual disability gene SETD5 disturbs developmental gene expression and cognition - Deliu, Elena; Arecco, Niccoló; Morandell, Jasmin; Dotter, Christoph; Contreras, Ximena; Girardot, Charles; Käsper, Eva; Kozlova, Alena; Kishi, Kasumi; Chiaradia, Ilaria; Noh, Kyung; Novarino, Gaia (Nature Neuroscience)
SETD5 gene mutations have been identified as a frequent cause of idiopathic intellectual disability. Here we show that Setd5-haploinsufficient mice present developmental defects such as abnormal brain-to-body weight ratios and neural crest defect-associated phenotypes. Furthermore, Setd5-mutant mice show impairments in cognitive tasks, enhanced long-term potentiation, delayed ontogenetic profile of ultrasonic vocalization, and behavioral inflexibility. Behavioral issues are accompanied by abnormal expression of postsynaptic density proteins previously associated with cognition. Our data additionally indicate that Setd5 regulates RNA polymerase II dynamics and gene transcription via its interaction with the Hdac3 and Paf1 complexes, findings potentially explaining the gene expression defects observed in Setd5-haploinsufficient mice. Our results emphasize the decisive role of Setd5 in a biological pathway found to be disrupted in humans with intellectual disability and autism spectrum disorder.

Indirect reciprocity with private, noisy, and incomplete information - Hilbe, Christian; Schmid, Laura; Tkadlec, Josef; Chatterjee, Krishnendu; Nowak, Martin (PNAS)
Indirect reciprocity explores how humans act when their reputation is at stake, and which social norms they use to assess the actions of others. A crucial question in indirect reciprocity is which social norms can maintain stable cooperation in a society. Past research has highlighted eight such norms, called “leading-eight” strategies. This past research, however, is based on the assumption that all relevant information about other population members is publicly available and that everyone agrees on who is good or bad. Instead, here we explore the reputation dynamics when information is private and noisy. We show that under these conditions, most leading-eight strategies fail to evolve. Those leading-eight strategies that do evolve are unable to sustain full cooperation.Indirect reciprocity is a mechanism for cooperation based on shared moral systems and individual reputations. It assumes that members of a community routinely observe and assess each other and that they use this information to decide who is good or bad, and who deserves cooperation. When information is transmitted publicly, such that all community members agree on each other’s reputation, previous research has highlighted eight crucial moral systems. These “leading-eight” strategies can maintain cooperation and resist invasion by defectors. However, in real populations individuals often hold their own private views of others. Once two individuals disagree about their opinion of some third party, they may also see its subsequent actions in a different light. Their opinions may further diverge over time. Herein, we explore indirect reciprocity when information transmission is private and noisy. We find that in the presence of perception errors, most leading-eight strategies cease to be stable. Even if a leading-eight strategy evolves, cooperation rates may drop considerably when errors are common. Our research highlights the role of reliable information and synchronized reputations to maintain stable moral systems.

Evolutionary potential of transcription factors for gene regulatory rewiring - Igler, Claudia; Lagator, Mato; Tkacik, Gasper; Bollback, Jonathan P; Guet, Calin C (Nature Ecology and Evolution)
Gene regulatory networks evolve through rewiring of individual components—that is, through changes in regulatory connections. However, the mechanistic basis of regulatory rewiring is poorly understood. Using a canonical gene regulatory system, we quantify the properties of transcription factors that determine the evolutionary potential for rewiring of regulatory connections: robustness, tunability and evolvability. In vivo repression measurements of two repressors at mutated operator sites reveal their contrasting evolutionary potential: while robustness and evolvability were positively correlated, both were in trade-off with tunability. Epistatic interactions between adjacent operators alleviated this trade-off. A thermodynamic model explains how the differences in robustness, tunability and evolvability arise from biophysical characteristics of repressor–DNA binding. The model also uncovers that the energy matrix, which describes how mutations affect repressor–DNA binding, encodes crucial information about the evolutionary potential of a repressor. The biophysical determinants of evolutionary potential for regulatory rewiring constitute a mechanistic framework for understanding network evolution.

Tetrode recording from the hippocampus of behaving mice coupled with four-point-irradiation closed-loop optogenetics: A technique to study the contribution of Hippocampal SWR events to learning - Rangel Guerrero, Dámaris K; Donnett, James G.; Csicsvari, Jozsef L; Kovács, Krisztián (eNeuro)
With the advent of optogenetics, it became possible to change the activity of a targeted population of neurons in a temporally controlled manner. To combine the advantages of 60-channel in vivo tetrode recording and laser-based optogenetics, we have developed a closed-loop recording system that allows for the actual electrophysiological signal to be used as a trigger for the laser light mediating the optogenetic intervention. We have optimized the weight, size, and shape of the corresponding implant to make it compatible with the size, force, and movements of a behaving mouse, and we have shown that the system can efficiently block sharp wave ripple (SWR) events using those events themselves as a trigger. To demonstrate the full potential of the optogenetic recording system we present a pilot study addressing the contribution of SWR events to learning in a complex behavioral task.

Viewpoint: Microwave quantum states beat the heat - Fink, Johannes M (Physics)
From microwave ovens to satellite television to the GPS and data services on our mobile phones, microwave technology is everywhere today. But one technology that has so far failed to prove its worth in this wavelength regime is quantum communication that uses the states of single photons as information carriers. This is because single microwave photons, as opposed to classical microwave signals, are extremely vulnerable to noise from thermal excitations in the channels through which they travel. Two new independent studies, one by Ze-Liang Xiang at Technische Universität Wien (Vienna), Austria, and colleagues [1] and another by Benoît Vermersch at the University of Innsbruck, also in Austria, and colleagues [2] now describe a theoretical protocol for microwave quantum communication that is resilient to thermal and other types of noise. Their approach could become a powerful technique to establish fast links between superconducting data processors in a future all-microwave quantum network.

A new proof rule for almost-sure termination - Mciver, Annabelle; Morgan, Carroll; Kaminski, Benjamin Lucien; Katoen, Joost P (Proceedings of the ACM on Programming Languages)
We present a new proof rule for proving almost-sure termination of probabilistic programs, including those that contain demonic non-determinism. An important question for a probabilistic program is whether the probability mass of all its diverging runs is zero, that is that it terminates "almost surely". Proving that can be hard, and this paper presents a new method for doing so. It applies directly to the program's source code, even if the program contains demonic choice. Like others, we use variant functions (a.k.a. "super-martingales") that are real-valued and decrease randomly on each loop iteration; but our key innovation is that the amount as well as the probability of the decrease are parametric. We prove the soundness of the new rule, indicate where its applicability goes beyond existing rules, and explain its connection to classical results on denumerable (non-demonic) Markov chains.

An application of stochastic differential equations to evolutionary algorithms - Paixao, Tiago; Pérez Heredia, Jorge (Proceedings of the 14th ACM/SIGEVO Conference on Foundations of Genetic Algorithms)
There has been renewed interest in modelling the behaviour of evolutionary algorithms by more traditional mathematical objects, such as ordinary differential equations or Markov chains. The advantage is that the analysis becomes greatly facilitated due to the existence of well established methods. However, this typically comes at the cost of disregarding information about the process. Here, we introduce the use of stochastic differential equations (SDEs) for the study of EAs. SDEs can produce simple analytical results for the dynamics of stochastic processes, unlike Markov chains which can produce rigorous but unwieldy expressions about the dynamics. On the other hand, unlike ordinary differential equations (ODEs), they do not discard information about the stochasticity of the process. We show that these are especially suitable for the analysis of fixed budget scenarios and present analogs of the additive and multiplicative drift theorems for SDEs. We exemplify the use of these methods for two model algorithms ((1+1) EA and RLS) on two canonical problems(OneMax and LeadingOnes).

Cumulative space in black-white pebbling and resolution - Alwen, Joel F; De Rezende, Susanna; Nordstrom, Jakob; Vinyals, Marc
We study space complexity and time-space trade-offs with a focus not on peak memory usage but on overall memory consumption throughout the computation. Such a cumulative space measure was introduced for the computational model of parallel black pebbling by [Alwen and Serbinenko ’15] as a tool for obtaining results in cryptography. We consider instead the non- deterministic black-white pebble game and prove optimal cumulative space lower bounds and trade-offs, where in order to minimize pebbling time the space has to remain large during a significant fraction of the pebbling. We also initiate the study of cumulative space in proof complexity, an area where other space complexity measures have been extensively studied during the last 10–15 years. Using and extending the connection between proof complexity and pebble games in [Ben-Sasson and Nordström ’08, ’11] we obtain several strong cumulative space results for (even parallel versions of) the resolution proof system, and outline some possible future directions of study of this, in our opinion, natural and interesting space measure.

Existence of traveling waves for the generalized F–KPP equation - Kollár, Richard; Novak, Sebastian (Bulletin of Mathematical Biology)
Variation in genotypes may be responsible for differences in dispersal rates, directional biases, and growth rates of individuals. These traits may favor certain genotypes and enhance their spatiotemporal spreading into areas occupied by the less advantageous genotypes. We study how these factors influence the speed of spreading in the case of two competing genotypes under the assumption that spatial variation of the total population is small compared to the spatial variation of the frequencies of the genotypes in the population. In that case, the dynamics of the frequency of one of the genotypes is approximately described by a generalized Fisher–Kolmogorov–Petrovskii–Piskunov (F–KPP) equation. This generalized F–KPP equation with (nonlinear) frequency-dependent diffusion and advection terms admits traveling wave solutions that characterize the invasion of the dominant genotype. Our existence results generalize the classical theory for traveling waves for the F–KPP with constant coefficients. Moreover, in the particular case of the quadratic (monostable) nonlinear growth–decay rate in the generalized F–KPP we study in detail the influence of the variance in diffusion and mean displacement rates of the two genotypes on the minimal wave propagation speed.

Unstable manifolds of relative periodic orbits in the symmetry reduced state space of the Kuramoto–Sivashinsky system - Budanur, Nazmi B; Cvitanović, Predrag (Journal of Statistical Physics)
Systems such as fluid flows in channels and pipes or the complex Ginzburg–Landau system, defined over periodic domains, exhibit both continuous symmetries, translational and rotational, as well as discrete symmetries under spatial reflections or complex conjugation. The simplest, and very common symmetry of this type is the equivariance of the defining equations under the orthogonal group O(2). We formulate a novel symmetry reduction scheme for such systems by combining the method of slices with invariant polynomial methods, and show how it works by applying it to the Kuramoto–Sivashinsky system in one spatial dimension. As an example, we track a relative periodic orbit through a sequence of bifurcations to the onset of chaos. Within the symmetry-reduced state space we are able to compute and visualize the unstable manifolds of relative periodic orbits, their torus bifurcations, a transition to chaos via torus breakdown, and heteroclinic connections between various relative periodic orbits. It would be very hard to carry through such analysis in the full state space, without a symmetry reduction such as the one we present here.

Hanani-Tutte for radial planarity - Fulek, Radoslav; Pelsmajer, Michael; Schaefer, Marcus (Journal of Graph Algorithms and Applications)
A drawing of a graph G is radial if the vertices of G are placed on concentric circles C 1 , . . . , C k with common center c , and edges are drawn radially : every edge intersects every circle centered at c at most once. G is radial planar if it has a radial embedding, that is, a crossing-free radial drawing. If the vertices of G are ordered or partitioned into ordered levels (as they are for leveled graphs), we require that the assignment of vertices to circles corresponds to the given ordering or leveling. We show that a graph G is radial planar if G has a radial drawing in which every two edges cross an even number of times; the radial embedding has the same leveling as the radial drawing. In other words, we establish the weak variant of the Hanani-Tutte theorem for radial planarity. This generalizes a result by Pach and Toth.

Structure of respiratory complex I: “Minimal” bacterial and “de luxe” mammalian versions - Sazanov, Leonid A (Mechanisms of primary energy transduction in biology)
Complex I (NADH:ubiquinone oxidoreductase) plays a central role in cellular energy generation, contributing to the proton motive force used to produce ATP. It couples the transfer of two electrons between NADH and quinone to translocation of four protons across the membrane. It is the largest protein assembly of bacterial and mitochondrial respiratory chains, composed, in mammals, of up to 45 subunits with a total molecular weight of ∼1 MDa. Bacterial enzyme is about half the size, providing the important “minimal” model of complex I. The l-shaped complex consists of a hydrophilic arm, where electron transfer occurs, and a membrane arm, where proton translocation takes place. Previously, we have solved the crystal structures of the hydrophilic domain of complex I from Thermus thermophilus and of the membrane domain from Escherichia coli, followed by the atomic structure of intact, entire complex I from T. thermophilus. Recently, we have solved by cryo-EM a first complete atomic structure of mammalian (ovine) mitochondrial complex I. Core subunits are well conserved from the bacterial version, whilst supernumerary subunits form an interlinked, stabilizing shell around the core. Subunits containing additional cofactors, including Zn ion, NADPH and phosphopantetheine, probably have regulatory roles. Dysfunction of mitochondrial complex I is implicated in many human neurodegenerative diseases. The structure of mammalian enzyme provides many insights into complex I mechanism, assembly, maturation and dysfunction, allowing detailed molecular analysis of disease-causing mutations.

Ensembles of bidirectional kinesin Cin8 produce additive forces in both directions of movement - Fallesen, Todd; Roostalu, Johanna; Düllberg, Christian F; Pruessner, Gunnar; Surrey, Thomas (Biophysical Journal)
Most kinesin motors move in only one direction along microtubules. Members of the kinesin-5 subfamily were initially described as unidirectional plus-end-directed motors and shown to produce piconewton forces. However, some fungal kinesin-5 motors are bidirectional. The force production of a bidirectional kinesin-5 has not yet been measured. Therefore, it remains unknown whether the mechanism of the unconventional minus-end-directed motility differs fundamentally from that of plus-end-directed stepping. Using force spectroscopy, we have measured here the forces that ensembles of purified budding yeast kinesin-5 Cin8 produce in microtubule gliding assays in both plus- and minus-end direction. Correlation analysis of pause forces demonstrated that individual Cin8 molecules produce additive forces in both directions of movement. In ensembles, Cin8 motors were able to produce single-motor forces up to a magnitude of ∼1.5 pN. Hence, these properties appear to be conserved within the kinesin-5 subfamily. Force production was largely independent of the directionality of movement, indicating similarities between the motility mechanisms for both directions. These results provide constraints for the development of models for the bidirectional motility mechanism of fission yeast kinesin-5 and provide insight into the function of this mitotic motor.

Improved algorithms for parity and Streett objectives - Chatterjee, Krishnendu; Henzinger, Monika H; Loitzenbauer, Veronika (Logical Methods in Computer Science)
The computation of the winning set for parity objectives and for Streett objectives in graphs as well as in game graphs are central problems in computer-aided verification, with application to the verification of closed systems with strong fairness conditions, the verification of open systems, checking interface compatibility, well-formedness of specifications, and the synthesis of reactive systems. We show how to compute the winning set on n vertices for (1) parity-3 (aka one-pair Streett) objectives in game graphs in time O(n5/2) and for (2) k-pair Streett objectives in graphs in time O(n2+nklogn). For both problems this gives faster algorithms for dense graphs and represents the first improvement in asymptotic running time in 15 years.

Water wave packets - Jeschke, Stefan; Wojtan, Christopher J (ACM Transactions on Graphics)
This paper presents a method for simulating water surface waves as a displacement field on a 2D domain. Our method relies on Lagrangian particles that carry packets of water wave energy; each packet carries information about an entire group of wave trains, as opposed to only a single wave crest. Our approach is unconditionally stable and can simulate high resolution geometric details. This approach also presents a straightforward interface for artistic control, because it is essentially a particle system with intuitive parameters like wavelength and amplitude. Our implementation parallelizes well and runs in real time for moderately challenging scenarios.

Faster statistical model checking for unbounded temporal properties - Daca, Przemyslaw; Henzinger, Thomas A; Kretinsky, Jan; Petrov, Tatjana (ACM Transactions on Computational Logic (TOCL))
We present a new algorithm for the statistical model checking of Markov chains with respect to unbounded temporal properties, including full linear temporal logic. The main idea is that we monitor each simulation run on the fly, in order to detect quickly if a bottom strongly connected component is entered with high probability, in which case the simulation run can be terminated early. As a result, our simulation runs are often much shorter than required by termination bounds that are computed a priori for a desired level of confidence on a large state space. In comparison to previous algorithms for statistical model checking our method is not only faster in many cases but also requires less information about the system, namely, only the minimum transition probability that occurs in the Markov chain. In addition, our method can be generalised to unbounded quantitative properties such as mean-payoff bounds.

Planar matchings for weighted straight skeletons - Biedl, Therese; Huber, Stefan; Palfrader, Peter (International Journal of Computational Geometry and Applications)
We introduce planar matchings on directed pseudo-line arrangements, which yield a planar set of pseudo-line segments such that only matching-partners are adjacent. By translating the planar matching problem into a corresponding stable roommates problem we show that such matchings always exist. Using our new framework, we establish, for the first time, a complete, rigorous definition of weighted straight skeletons, which are based on a so-called wavefront propagation process. We present a generalized and unified approach to treat structural changes in the wavefront that focuses on the restoration of weak planarity by finding planar matchings.

Bogoliubov correction to the mean-field dynamics of interacting bosons - Nam, Phan; Napiórkowski, Marcin M (Advances in Theoretical and Mathematical Physics)
We consider the dynamics of a large quantum system of N identical bosons in 3D interacting via a two-body potential of the form N3β-1w(Nβ(x - y)). For fixed 0 = β < 1/3 and large N, we obtain a norm approximation to the many-body evolution in the Nparticle Hilbert space. The leading order behaviour of the dynamics is determined by Hartree theory while the second order is given by Bogoliubov theory.

Universality for a class of random band matrices - Bourgade, Paul; Erdös, László; Yau, Horng; Yin, Jun (Advances in Theoretical and Mathematical Physics)
We prove the universality for the eigenvalue gap statistics in the bulk of the spectrum for band matrices, in the regime where the band width is comparable with the dimension of the matrix, W ~ N. All previous results concerning universality of non-Gaussian random matrices are for mean-field models. By relying on a new mean-field reduction technique, we deduce universality from quantum unique ergodicity for band matrices.

Towards unlicensed cellular networks in TV white spaces - Baig, Ghufran; Radunovic, Bozidar; Alistarh, Dan-Adrian; Balkwill, Matthew; Karagiannis, Thomas; Qiu, Lili (Proceedings of the 2017 13th International Conference on emerging Networking EXperiments and Technologies)
In this paper we study network architecture for unlicensed cellular networking for outdoor coverage in TV white spaces. The main technology proposed for TV white spaces is 802.11af, a Wi-Fi variant adapted for TV frequencies. However, 802.11af is originally designed for improved indoor propagation. We show that long links, typical for outdoor use, exacerbate known Wi-Fi issues, such as hidden and exposed terminal, and significantly reduce its efficiency. Instead, we propose CellFi, an alternative architecture based on LTE. LTE is designed for long-range coverage and throughput efficiency, but it is also designed to operate in tightly controlled and centrally managed networks. CellFi overcomes these problems by designing an LTE-compatible spectrum database component, mandatory for TV white space networking, and introducing an interference management component for distributed coordination. CellFi interference management is compatible with existing LTE mechanisms, requires no explicit communication between base stations, and is more efficient than CSMA for long links. We evaluate our design through extensive real world evaluation on of-the-shelf LTE equipment and simulations. We show that, compared to 802.11af, it increases coverage by 40% and reduces median flow completion times by 2.3x.

Activity dependent feedback inhibition may maintain head direction signals in mouse presubiculum - Simonnet, Jean; Nassar, Mérie; Stella, Federico; Cohen, Ivan; Mathon, Bertrand; Boccara, Charlotte; Miles, Richard; Fricker, Desdemona (Nature Communications)
Orientation in space is represented in specialized brain circuits. Persistent head direction signals are transmitted from anterior thalamus to the presubiculum, but the identity of the presubicular target neurons, their connectivity and function in local microcircuits are unknown. Here, we examine how thalamic afferents recruit presubicular principal neurons and Martinotti interneurons, and the ensuing synaptic interactions between these cells. Pyramidal neuron activation of Martinotti cells in superficial layers is strongly facilitating such that high-frequency head directional stimulation efficiently unmutes synaptic excitation. Martinotti-cell feedback plays a dual role: precisely timed spikes may not inhibit the firing of in-tune head direction cells, while exerting lateral inhibition. Autonomous attractor dynamics emerge from a modelled network implementing wiring motifs and timing sensitive synaptic interactions in the pyramidal - Martinotti-cell feedback loop. This inhibitory microcircuit is therefore tuned to refine and maintain head direction information in the presubiculum.

Clarifying the supercomplex: The higher-order organization of the mitochondrial electron transport chain - Letts, James A; Sazanov, Leonid A (Nature Structural and Molecular Biology)
The oxidative phosphorylation electron transport chain (OXPHOS-ETC) of the inner mitochondrial membrane is composed of five large protein complexes, named CI-CV. These complexes convert energy from the food we eat into ATP, a small molecule used to power a multitude of essential reactions throughout the cell. OXPHOS-ETC complexes are organized into supercomplexes (SCs) of defined stoichiometry: CI forms a supercomplex with CIII2 and CIV (SC I+III2+IV, known as the respirasome), as well as with CIII2 alone (SC I+III2). CIII2 forms a supercomplex with CIV (SC III2+IV) and CV forms dimers (CV2). Recent cryo-EM studies have revealed the structures of SC I+III2+IV and SC I+III2. Furthermore, recent work has shed light on the assembly and function of the SCs. Here we review and compare these recent studies and discuss how they have advanced our understanding of mitochondrial electron transport.

Couette-Poiseuille flow experiment with zero mean advection velocity: Subcritical transition to turbulence - Klotz, Lukasz; Lemoult, Grégoire M; Frontczak, Idalia; Tuckerman, Laurette; Wesfreid, José (Physical Review Fluids)
We present an experimental setup that creates a shear flow with zero mean advection velocity achieved by counterbalancing the nonzero streamwise pressure gradient by moving boundaries, which generates plane Couette-Poiseuille flow. We obtain experimental results in the transitional regime for this flow. Using flow visualization, we characterize the subcritical transition to turbulence in Couette-Poiseuille flow and show the existence of turbulent spots generated by a permanent perturbation. Due to the zero mean advection velocity of the base profile, these turbulent structures are nearly stationary. We distinguish two regions of the turbulent spot: the active turbulent core, which is characterized by waviness of the streaks similar to traveling waves, and the surrounding region, which includes in addition the weak undisturbed streaks and oblique waves at the laminar-turbulent interface. We also study the dependence of the size of these two regions on Reynolds number. Finally, we show that the traveling waves move in the downstream (Poiseuille) direction.

Nonhierarchical flux regulation exposes the fitness burden associated with lactate production in Synechocystis sp. PCC6803 - Du, Wei; Angermayr, Andreas; Jongbloets, Joeri; Molenaar, Douwe; Bachmann, Herwig; Hellingwerf, Klaas; Branco Dos Santos, Filipe (ACS Synthetic Biology)
Cyanobacteria are mostly engineered to be sustainable cell-factories by genetic manipulations alone. Here, by modulating the concentration of allosteric effectors, we focus on increasing product formation without further burdening the cells with increased expression of enzymes. Resorting to a novel 96-well microplate cultivation system for cyanobacteria, and using lactate-producing strains of Synechocystis PCC6803 expressing different l-lactate dehydrogenases (LDH), we titrated the effect of 2,5-anhydro-mannitol supplementation. The latter acts in cells as a nonmetabolizable analogue of fructose 1,6-bisphosphate, a known allosteric regulator of one of the tested LDHs. In this strain (SAA023), we achieved over 2-fold increase of lactate productivity. Furthermore, we observed that as carbon is increasingly deviated during growth toward product formation, there is an increased fixation rate in the population of spontaneous mutants harboring an impaired production pathway. This is a challenge in the development of green cell factories, which may be countered by the incorporation in biotechnological processes of strategies such as the one pioneered here.

Higson compactification and dimension raising - Austin, Kyle; Virk, Ziga (Topology and its Applications)
Let X and Y be proper metric spaces. We show that a coarsely n-to-1 map f:X→Y induces an n-to-1 map of Higson coronas. This viewpoint turns out to be successful in showing that the classical dimension raising theorems hold in large scale; that is, if f:X→Y is a coarsely n-to-1 map between proper metric spaces X and Y then asdim(Y)≤asdim(X)+n−1. Furthermore we introduce coarsely open coarsely n-to-1 maps, which include the natural quotient maps via a finite group action, and prove that they preserve the asymptotic dimension.

Finding non-orientable surfaces in 3-Manifolds - Burton, Benjamin; De Mesmay, Arnaud N; Wagner, Uli (Discrete & Computational Geometry)
We investigate the complexity of finding an embedded non-orientable surface of Euler genus g in a triangulated 3-manifold. This problem occurs both as a natural question in low-dimensional topology, and as a first non-trivial instance of embeddability of complexes into 3-manifolds. We prove that the problem is NP-hard, thus adding to the relatively few hardness results that are currently known in 3-manifold topology. In addition, we show that the problem lies in NP when the Euler genus g is odd, and we give an explicit algorithm in this case.

Grünlicht-induzierte Rezeptorinaktivierung durch Cobalamin-bindende Domänen - Kainrath, Stephanie; Stadler, Manuela; Gschaider-Reichhart, Eva; Distel, Martin; Janovjak, Harald L (Angewandte Chemie)
Optogenetik und Photopharmakologie ermöglichen präzise räumliche und zeitliche Kontrolle von Proteinwechselwirkung und -funktion in Zellen und Tieren. Optogenetische Methoden, die auf grünes Licht ansprechen und zum Trennen von Proteinkomplexen geeignet sind, sind nichtweitläufig verfügbar, würden jedoch mehrfarbige Experimente zur Beantwortung von biologischen Fragestellungen ermöglichen. Hier demonstrieren wir die Verwendung von Cobalamin(Vitamin B12)-bindenden Domänen von bakteriellen CarH-Transkriptionsfaktoren zur Grünlicht-induzierten Dissoziation von Rezeptoren. Fusioniert mit dem Fibroblasten-W achstumsfaktor-Rezeptor 1 führten diese im Dunkeln in kultivierten Zellen zu Signalaktivität durch Oligomerisierung, welche durch Beleuchten umgehend aufgehoben wurde. In Zebrafischembryonen, die einen derartigen Rezeptor exprimieren, ermöglichte grünes Licht die Kontrolle über abnormale Signalaktivität während der Embryonalentwicklung.

Characterization of host proteins interacting with the lymphocytic choriomeningitis virus L protein - Khamina, Kseniya; Lercher, Alexander; Caldera, Michael; Schliehe, Christopher; Vilagos, Bojan; Sahin, Mehmet; Kosack, Lindsay; Bhattacharya, Anannya; Májek, Peter; Stukalov, Alexey; Sacco, Roberto; James, Leo; et al. (PLoS Pathogens)
RNA-dependent RNA polymerases (RdRps) play a key role in the life cycle of RNA viruses and impact their immunobiology. The arenavirus lymphocytic choriomeningitis virus (LCMV) strain Clone 13 provides a benchmark model for studying chronic infection. A major genetic determinant for its ability to persist maps to a single amino acid exchange in the viral L protein, which exhibits RdRp activity, yet its functional consequences remain elusive. To unravel the L protein interactions with the host proteome, we engineered infectious L protein-tagged LCMV virions by reverse genetics. A subsequent mass-spectrometric analysis of L protein pulldowns from infected human cells revealed a comprehensive network of interacting host proteins. The obtained LCMV L protein interactome was bioinformatically integrated with known host protein interactors of RdRps from other RNA viruses, emphasizing interconnected modules of human proteins. Functional characterization of selected interactors highlighted proviral (DDX3X) as well as antiviral (NKRF, TRIM21) host factors. To corroborate these findings, we infected Trim21-/-mice with LCMV and found impaired virus control in chronic infection. These results provide insights into the complex interactions of the arenavirus LCMV and other viral RdRps with the host proteome and contribute to a better molecular understanding of how chronic viruses interact with their host.

Unifying two views on multiple mean-payoff objectives in Markov decision processes - Chatterjee, Krishnendu; Křetínská, Zuzana; Kretinsky, Jan (Logical Methods in Computer Science)
We consider Markov decision processes (MDPs) with multiple limit-average (or mean-payoff) objectives. There exist two different views: (i) the expectation semantics, where the goal is to optimize the expected mean-payoff objective, and (ii) the satisfaction semantics, where the goal is to maximize the probability of runs such that the mean-payoff value stays above a given vector. We consider optimization with respect to both objectives at once, thus unifying the existing semantics. Precisely, the goal is to optimize the expectation while ensuring the satisfaction constraint. Our problem captures the notion of optimization with respect to strategies that are risk-averse (i.e., ensure certain probabilistic guarantee). Our main results are as follows: First, we present algorithms for the decision problems which are always polynomial in the size of the MDP. We also show that an approximation of the Pareto-curve can be computed in time polynomial in the size of the MDP, and the approximation factor, but exponential in the number of dimensions. Second, we present a complete characterization of the strategy complexity (in terms of memory bounds and randomization) required to solve our problem.

Nested weighted automata - Chatterjee, Krishnendu; Henzinger, Thomas A; Otop, Jan (ACM Transactions on Computational Logic (TOCL))
Recently there has been a significant effort to handle quantitative properties in formal verification and synthesis. While weighted automata over finite and infinite words provide a natural and flexible framework to express quantitative properties, perhaps surprisingly, some basic system properties such as average response time cannot be expressed using weighted automata or in any other known decidable formalism. In this work, we introduce nested weighted automata as a natural extension of weighted automata, which makes it possible to express important quantitative properties such as average response time. In nested weighted automata, a master automaton spins off and collects results from weighted slave automata, each of which computes a quantity along a finite portion of an infinite word. Nested weighted automata can be viewed as the quantitative analogue of monitor automata, which are used in runtime verification. We establish an almost-complete decidability picture for the basic decision problems about nested weighted automata and illustrate their applicability in several domains. In particular, nested weighted automata can be used to decide average response time properties.

Edit distance for pushdown automata - Chatterjee, Krishnendu; Henzinger, Thomas A; Ibsen-Jensen, Rasmus; Otop, Jan (Logical Methods in Computer Science)
The edit distance between two words w 1 , w 2 is the minimal number of word operations (letter insertions, deletions, and substitutions) necessary to transform w 1 to w 2 . The edit distance generalizes to languages L 1 , L 2 , where the edit distance from L 1 to L 2 is the minimal number k such that for every word from L 1 there exists a word in L 2 with edit distance at most k . We study the edit distance computation problem between pushdown automata and their subclasses. The problem of computing edit distance to a pushdown automaton is undecidable, and in practice, the interesting question is to compute the edit distance from a pushdown automaton (the implementation, a standard model for programs with recursion) to a regular language (the specification). In this work, we present a complete picture of decidability and complexity for the following problems: (1) deciding whether, for a given threshold k , the edit distance from a pushdown automaton to a finite automaton is at most k , and (2) deciding whether the edit distance from a pushdown automaton to a finite automaton is finite.

Amplification on undirected population structures: Comets beat stars - Pavlogiannis, Andreas; Tkadlec, Josef; Chatterjee, Krishnendu; Nowak, Martin (Scientific Reports)
The fixation probability is the probability that a new mutant introduced in a homogeneous population eventually takes over the entire population. The fixation probability is a fundamental quantity of natural selection, and known to depend on the population structure. Amplifiers of natural selection are population structures which increase the fixation probability of advantageous mutants, as compared to the baseline case of well-mixed populations. In this work we focus on symmetric population structures represented as undirected graphs. In the regime of undirected graphs, the strongest amplifier known has been the Star graph, and the existence of undirected graphs with stronger amplification properties has remained open for over a decade. In this work we present the Comet and Comet-swarm families of undirected graphs. We show that for a range of fitness values of the mutants, the Comet and Cometswarm graphs have fixation probability strictly larger than the fixation probability of the Star graph, for fixed population size and at the limit of large populations, respectively.

Optimal Dyck reachability for data-dependence and Alias analysis - Chatterjee, Krishnendu; Choudhary, Bhavya; Pavlogiannis, Andreas (Proceedings of the ACM on Programming Languages)
A fundamental algorithmic problem at the heart of static analysis is Dyck reachability. The input is a graph where the edges are labeled with different types of opening and closing parentheses, and the reachability information is computed via paths whose parentheses are properly matched. We present new results for Dyck reachability problems with applications to alias analysis and data-dependence analysis. Our main contributions, that include improved upper bounds as well as lower bounds that establish optimality guarantees, are as follows: First, we consider Dyck reachability on bidirected graphs, which is the standard way of performing field-sensitive points-to analysis. Given a bidirected graph with n nodes and m edges, we present: (i) an algorithm with worst-case running time O(m + n · α(n)), where α(n) is the inverse Ackermann function, improving the previously known O(n2) time bound; (ii) a matching lower bound that shows that our algorithm is optimal wrt to worst-case complexity; and (iii) an optimal average-case upper bound of O(m) time, improving the previously known O(m · logn) bound. Second, we consider the problem of context-sensitive data-dependence analysis, where the task is to obtain analysis summaries of library code in the presence of callbacks. Our algorithm preprocesses libraries in almost linear time, after which the contribution of the library in the complexity of the client analysis is only linear, and only wrt the number of call sites. Third, we prove that combinatorial algorithms for Dyck reachability on general graphs with truly sub-cubic bounds cannot be obtained without obtaining sub-cubic combinatorial algorithms for Boolean Matrix Multiplication, which is a long-standing open problem. Thus we establish that the existing combinatorial algorithms for Dyck reachability are (conditionally) optimal for general graphs. We also show that the same hardness holds for graphs of constant treewidth. Finally, we provide a prototype implementation of our algorithms for both alias analysis and data-dependence analysis. Our experimental evaluation demonstrates that the new algorithms significantly outperform all existing methods on the two problems, over real-world benchmarks.

Optimal Dyck reachability for data-dependence and alias analysis - Chatterjee, Krishnendu; Choudhary, Bhavya; Pavlogiannis, Andreas
A fundamental algorithmic problem at the heart of static analysis is Dyck reachability. The input is a graphwhere the edges are labeled with different types of opening and closing parentheses, and the reachabilityinformation is computed via paths whose parentheses are properly matched. We present new results for Dyckreachability problems with applications to alias analysis and data-dependence analysis. Our main contributions,that include improved upper bounds as well as lower bounds that establish optimality guarantees, are asfollows:First, we consider Dyck reachability on bidirected graphs, which is the standard way of performing field-sensitive points-to analysis. Given a bidirected graph withnnodes andmedges, we present: (i) an algorithmwith worst-case running timeO(m+n·α(n)), whereα(n)is the inverse Ackermann function, improving thepreviously knownO(n2)time bound; (ii) a matching lower bound that shows that our algorithm is optimalwrt to worst-case complexity; and (iii) an optimal average-case upper bound ofO(m)time, improving thepreviously knownO(m·logn)bound.Second, we consider the problem of context-sensitive data-dependence analysis, where the task is to obtainanalysis summaries of library code in the presence of callbacks. Our algorithm preprocesses libraries in almostlinear time, after which the contribution of the library in the complexity of the client analysis is only linear,and only wrt the number of call sites.Third, we prove that combinatorial algorithms for Dyck reachability on general graphs with truly sub-cubic bounds cannot be obtained without obtaining sub-cubic combinatorial algorithms for Boolean MatrixMultiplication, which is a long-standing open problem. Thus we establish that the existing combinatorialalgorithms for Dyck reachability are (conditionally) optimal for general graphs. We also show that the samehardness holds for graphs of constant treewidth.Finally, we provide a prototype implementation of our algorithms for both alias analysis and data-dependenceanalysis. Our experimental evaluation demonstrates that the new algorithms significantly outperform allexisting methods on the two problems, over real-world benchmarks.

Data-centric dynamic partial order reduction - Chalupa, Marek; Chatterjee, Krishnendu; Pavlogiannis, Andreas; Sinha, Nishant; Vaidya, Kapil (Proceedings of the ACM on Programming Languages)
We present a new dynamic partial-order reduction method for stateless model checking of concurrent programs. A common approach for exploring program behaviors relies on enumerating the traces of the program, without storing the visited states (aka stateless exploration). As the number of distinct traces grows exponentially, dynamic partial-order reduction (DPOR) techniques have been successfully used to partition the space of traces into equivalence classes (Mazurkiewicz partitioning), with the goal of exploring only few representative traces from each class. We introduce a new equivalence on traces under sequential consistency semantics, which we call the observation equivalence. Two traces are observationally equivalent if every read event observes the same write event in both traces. While the traditional Mazurkiewicz equivalence is control-centric, our new definition is data-centric. We show that our observation equivalence is coarser than the Mazurkiewicz equivalence, and in many cases even exponentially coarser. We devise a DPOR exploration of the trace space, called data-centric DPOR, based on the observation equivalence.

Data-centric dynamic partial order reduction - Chalupa, Marek; Chatterjee, Krishnendu; Pavlogiannis, Andreas; Sinha, Nishant; Vaidya, Kapil
We present a new dynamic partial-order reduction method for stateless model checking of concurrent programs. A common approach for exploring program behaviors relies on enumerating the traces of the program, without storing the visited states (aka stateless exploration). As the number of distinct traces grows exponentially, dynamic partial-order reduction (DPOR) techniques have been successfully used to partition the space of traces into equivalence classes (Mazurkiewicz partitioning), with the goal of exploring only few representative traces from each class. We introduce a new equivalence on traces under sequential consistency semantics, which we call the observation equivalence. Two traces are observationally equivalent if every read event observes the same write event in both traces. While the traditional Mazurkiewicz equivalence is control-centric, our new definition is data-centric. We show that our observation equivalence is coarser than the Mazurkiewicz equivalence, and in many cases even exponentially coarser. We devise a DPOR exploration of the trace space, called data-centric DPOR, based on the observation equivalence. 1. For acyclic architectures, our algorithm is guaranteed to explore exactly one representative trace from each observation class, while spending polynomial time per class. Hence, our algorithm is optimal wrt the observation equivalence, and in several cases explores exponentially fewer traces than any enumerative method based on the Mazurkiewicz equivalence. 2. For cyclic architectures, we consider an equivalence between traces which is finer than the observation equivalence; but coarser than the Mazurkiewicz equivalence, and in some cases is exponentially coarser. Our data-centric DPOR algorithm remains optimal under this trace equivalence. Finally, we perform a basic experimental comparison between the existing Mazurkiewicz-based DPOR and our data-centric DPOR on a set of academic benchmarks. Our results show a significant reduction in both running time and the number of explored equivalence classes.

Faster Monte Carlo algorithms for fixation probability of the Moran process on undirected graphs - Chatterjee, Krishnendu; Ibsen-Jensen, Rasmus; Nowak, Martin (Leibniz International Proceedings in Informatics)
Evolutionary graph theory studies the evolutionary dynamics in a population structure given as a connected graph. Each node of the graph represents an individual of the population, and edges determine how offspring are placed. We consider the classical birth-death Moran process where there are two types of individuals, namely, the residents with fitness 1 and mutants with fitness r. The fitness indicates the reproductive strength. The evolutionary dynamics happens as follows: in the initial step, in a population of all resident individuals a mutant is introduced, and then at each step, an individual is chosen proportional to the fitness of its type to reproduce, and the offspring replaces a neighbor uniformly at random. The process stops when all individuals are either residents or mutants. The probability that all individuals in the end are mutants is called the fixation probability, which is a key factor in the rate of evolution. We consider the problem of approximating the fixation probability. The class of algorithms that is extremely relevant for approximation of the fixation probabilities is the Monte-Carlo simulation of the process. Previous results present a polynomial-time Monte-Carlo algorithm for undirected graphs when r is given in unary. First, we present a simple modification: instead of simulating each step, we discard ineffective steps, where no node changes type (i.e., either residents replace residents, or mutants replace mutants). Using the above simple modification and our result that the number of effective steps is concentrated around the expected number of effective steps, we present faster polynomial-time Monte-Carlo algorithms for undirected graphs. Our algorithms are always at least a factor O(n2/ log n) faster as compared to the previous algorithms, where n is the number of nodes, and is polynomial even if r is given in binary. We also present lower bounds showing that the upper bound on the expected number of effective steps we present is asymptotically tight for undirected graphs.

Faster algorithms for mean-payoff parity games - Chatterjee, Krishnendu; Henzinger, Monika H; Svozil, Alexander (Leibniz International Proceedings in Informatics)
Graph games provide the foundation for modeling and synthesis of reactive processes. Such games are played over graphs where the vertices are controlled by two adversarial players. We consider graph games where the objective of the first player is the conjunction of a qualitative objective (specified as a parity condition) and a quantitative objective (specified as a meanpayoff condition). There are two variants of the problem, namely, the threshold problem where the quantitative goal is to ensure that the mean-payoff value is above a threshold, and the value problem where the quantitative goal is to ensure the optimal mean-payoff value; in both cases ensuring the qualitative parity objective. The previous best-known algorithms for game graphs with n vertices, m edges, parity objectives with d priorities, and maximal absolute reward value W for mean-payoff objectives, are as follows: O(nd+1 . m . w) for the threshold problem, and O(nd+2 · m · W) for the value problem. Our main contributions are faster algorithms, and the running times of our algorithms are as follows: O(nd-1 · m ·W) for the threshold problem, and O(nd · m · W · log(n · W)) for the value problem. For mean-payoff parity objectives with two priorities, our algorithms match the best-known bounds of the algorithms for mean-payoff games (without conjunction with parity objectives). Our results are relevant in synthesis of reactive systems with both functional requirement (given as a qualitative objective) and performance requirement (given as a quantitative objective).

Strategy complexity of concurrent safety games - Chatterjee, Krishnendu; Hansen, Kristofer; Ibsen-Jensen, Rasmus (Leibniz International Proceedings in Informatics)
We consider two player, zero-sum, finite-state concurrent reachability games, played for an infinite number of rounds, where in every round, each player simultaneously and independently of the other players chooses an action, whereafter the successor state is determined by a probability distribution given by the current state and the chosen actions. Player 1 wins iff a designated goal state is eventually visited. We are interested in the complexity of stationary strategies measured by their patience, which is defined as the inverse of the smallest non-zero probability employed. Our main results are as follows: We show that: (i) the optimal bound on the patience of optimal and -optimal strategies, for both players is doubly exponential; and (ii) even in games with a single non-absorbing state exponential (in the number of actions) patience is necessary.

On stochastic differential equations with arbitrarily slow convergence rates for strong approximation in two space dimensions - Gerencser, Mate; Jentzen, Arnulf; Salimova, Diyora (Proceedings of the Royal Society A: Mathematical, Physical and Engineering Sciences)
In a recent article (Jentzen et al. 2016 Commun. Math. Sci. 14, 1477–1500 (doi:10.4310/CMS.2016.v14. n6.a1)), it has been established that, for every arbitrarily slow convergence speed and every natural number d ? {4, 5, . . .}, there exist d-dimensional stochastic differential equations with infinitely often differentiable and globally bounded coefficients such that no approximation method based on finitely many observations of the driving Brownian motion can converge in absolute mean to the solution faster than the given speed of convergence. In this paper, we strengthen the above result by proving that this slow convergence phenomenon also arises in two (d = 2) and three (d = 3) space dimensions.

A Dynamical Approach to Random Matrix Theory - Erdös, László; Yau, Horng
This book is a concise and self-contained introduction of recent techniques to prove local spectral universality for large random matrices. Random matrix theory is a fast expanding research area, and this book mainly focuses on the methods that the authors participated in developing over the past few years. Many other interesting topics are not included, and neither are several new developments within the framework of these methods. The authors have chosen instead to present key concepts that they believe are the core of these methods and should be relevant for future applications. They keep technicalities to a minimum to make the book accessible to graduate students. With this in mind, they include in this book the basic notions and tools for high-dimensional analysis, such as large deviation, entropy, Dirichlet form, and the logarithmic Sobolev inequality.

Persistence of zero sets - Franek, Peter; Krcál, Marek (Homology, Homotopy and Applications)
We study robust properties of zero sets of continuous maps f: X → ℝn. Formally, we analyze the family Z< r(f) := (g-1(0): ||g - f|| < r) of all zero sets of all continuous maps g closer to f than r in the max-norm. All of these sets are outside A := (x: |f(x)| ≥ r) and we claim that Z< r(f) is fully determined by A and an element of a certain cohomotopy group which (by a recent result) is computable whenever the dimension of X is at most 2n - 3. By considering all r > 0 simultaneously, the pointed cohomotopy groups form a persistence module-a structure leading to persistence diagrams as in the case of persistent homology or well groups. Eventually, we get a descriptor of persistent robust properties of zero sets that has better descriptive power (Theorem A) and better computability status (Theorem B) than the established well diagrams. Moreover, if we endow every point of each zero set with gradients of the perturbation, the robust description of the zero sets by elements of cohomotopy groups is in some sense the best possible (Theorem C).

Regulatory network structure determines patterns of intermolecular epistasis - Lagator, Mato; Sarikas, Srdjan; Acar, Hande; Bollback, Jonathan P; Guet, Calin C (eLife)
Most phenotypes are determined by molecular systems composed of specifically interacting molecules. However, unlike for individual components, little is known about the distributions of mutational effects of molecular systems as a whole. We ask how the distribution of mutational effects of a transcriptional regulatory system differs from the distributions of its components, by first independently, and then simultaneously, mutating a transcription factor and the associated promoter it represses. We find that the system distribution exhibits increased phenotypic variation compared to individual component distributions - an effect arising from intermolecular epistasis between the transcription factor and its DNA-binding site. In large part, this epistasis can be qualitatively attributed to the structure of the transcriptional regulatory system and could therefore be a common feature in prokaryotes. Counter-intuitively, intermolecular epistasis can alleviate the constraints of individual components, thereby increasing phenotypic variation that selection could act on and facilitating adaptive evolution.

Cytokinesis in vertebrate cells initiates by contraction of an equatorial actomyosin network composed of randomly oriented filaments - Spira, Felix; Cuylen Haering, Sara; Mehta, Shalin; Samwer, Matthias; Reversat, Anne; Verma, Amitabh; Oldenbourg, Rudolf; Sixt, Michael K; Gerlich, Daniel (eLife)
The actomyosin ring generates force to ingress the cytokinetic cleavage furrow in animal cells, yet its filament organization and the mechanism of contractility is not well understood. We quantified actin filament order in human cells using fluorescence polarization microscopy and found that cleavage furrow ingression initiates by contraction of an equatorial actin network with randomly oriented filaments. The network subsequently gradually reoriented actin filaments along the cell equator. This strictly depended on myosin II activity, suggesting local network reorganization by mechanical forces. Cortical laser microsurgery revealed that during cytokinesis progression, mechanical tension increased substantially along the direction of the cell equator, while the network contracted laterally along the pole-to-pole axis without a detectable increase in tension. Our data suggest that an asymmetric increase in cortical tension promotes filament reorientation along the cytokinetic cleavage furrow, which might have implications for diverse other biological processes involving actomyosin rings.

Migrating platelets are mechano scavengers that collect and bundle bacteria - Gärtner, Florian R; Ahmad, Zerkah; Rosenberger, Gerhild; Fan, Shuxia; Nicolai, Leo; Busch, Benjamin; Yavuz, Gökce; Luckner, Manja; Ishikawa Ankerhold, Hellen; Hennel, Roman; Benechet, Alexandre; Lorenz, Michael; et al. (Cell Press)
Blood platelets are critical for hemostasis and thrombosis and play diverse roles during immune responses. Despite these versatile tasks in mammalian biology, their skills on a cellular level are deemed limited, mainly consisting in rolling, adhesion, and aggregate formation. Here, we identify an unappreciated asset of platelets and show that adherent platelets use adhesion receptors to mechanically probe the adhesive substrate in their local microenvironment. When actomyosin-dependent traction forces overcome substrate resistance, platelets migrate and pile up the adhesive substrate together with any bound particulate material. They use this ability to act as cellular scavengers, scanning the vascular surface for potential invaders and collecting deposited bacteria. Microbe collection by migrating platelets boosts the activity of professional phagocytes, exacerbating inflammatory tissue injury in sepsis. This assigns platelets a central role in innate immune responses and identifies them as potential targets to dampen inflammatory tissue damage in clinical scenarios of severe systemic infection. In addition to their role in thrombosis and hemostasis, platelets can also migrate to sites of infection to help trap bacteria and clear the vascular surface.

Control of endogenous auxin levels in plant root development - Olatunji, Damilola; Geelen, Danny; Verstraeten, Inge (International Journal of Molecular Sciences)
In this review, we summarize the different biosynthesis-related pathways that contribute to the regulation of endogenous auxin in plants. We demonstrate that all known genes involved in auxin biosynthesis also have a role in root formation, from the initiation of a root meristem during embryogenesis to the generation of a functional root system with a primary root, secondary lateral root branches and adventitious roots. Furthermore, the versatile adaptation of root development in response to environmental challenges is mediated by both local and distant control of auxin biosynthesis. In conclusion, auxin homeostasis mediated by spatial and temporal regulation of auxin biosynthesis plays a central role in determining root architecture.

Construction of persistent Voronoi diagram on 3D digital plane - Biswas, Ranita; Bhowmick, Partha (Combinatorial image analysis)
Different distance metrics produce Voronoi diagrams with different properties. It is a well-known that on the (real) 2D plane or even on any 3D plane, a Voronoi diagram (VD) based on the Euclidean distance metric produces convex Voronoi regions. In this paper, we first show that this metric produces a persistent VD on the 2D digital plane, as it comprises digitally convex Voronoi regions and hence correctly approximates the corresponding VD on the 2D real plane. Next, we show that on a 3D digital plane D, the Euclidean metric spanning over its voxel set does not guarantee a digital VD which is persistent with the real-space VD. As a solution, we introduce a novel concept of functional-plane-convexity, which is ensured by the Euclidean metric spanning over the pedal set of D. Necessary proofs and some visual result have been provided to adjudge the merit and usefulness of the proposed concept.

Experimental evidence for Wigner's tunneling time - Camus, Nicolas; Yakaboylu, Enderalp; Fechner, Lutz; Klaiber, Michael; Laux, Martin; Mi, Yonghao; Hatsagortsyan, Karen; Pfeifer, Thomas; Keitel, Cristoph; Moshammer, Robert
Tunneling of a particle through a potential barrier remains one of the most remarkable quantum phenomena. Owing to advances in laser technology, electric fields comparable to those electrons experience in atoms are readily generated and open opportunities to dynamically investigate the process of electron tunneling through the potential barrier formed by the superposition of both laser and atomic fields. Attosecond-time and angstrom-space resolution of the strong laser-field technique allow to address fundamental questions related to tunneling, which are still open and debated: Which time is spent under the barrier and what momentum is picked up by the particle in the meantime? In this combined experimental and theoretical study we demonstrate that for strong-field ionization the leading quantum mechanical Wigner treatment for the time resolved description of tunneling is valid. We achieve a high sensitivity on the tunneling barrier and unambiguously isolate its effects by performing a differential study of two systems with almost identical tunneling geometry. Moreover, working with a low frequency laser, we essentially limit the non-adiabaticity of the process as a major source of uncertainty. The agreement between experiment and theory implies two substantial corrections with respect to the widely employed quasiclassical treatment: In addition to a non-vanishing longitudinal momentum along the laser field-direction we provide clear evidence for a non-zero tunneling time delay. This addresses also the fundamental question how the transition occurs from the tunnel barrier to free space classical evolution of the ejected electron.

Experimental evidence for quantum tunneling time - Camus, Nicolas; Yakaboylu, Enderalp; Fechner, Lutz; Klaiber, Michael; Laux, Martin; Mi, Yonghao; Hatsagortsyan, Karen Z.; Pfeifer, Thomas; Keitel, Christoph H.; Moshammer, Robert (Physical Review Letters)
The first hundred attoseconds of the electron dynamics during strong field tunneling ionization are investigated. We quantify theoretically how the electron’s classical trajectories in the continuum emerge from the tunneling process and test the results with those achieved in parallel from attoclock measurements. An especially high sensitivity on the tunneling barrier is accomplished here by comparing the momentum distributions of two atomic species of slightly deviating atomic potentials (argon and krypton) being ionized under absolutely identical conditions with near-infrared laser pulses (1300 nm). The agreement between experiment and theory provides clear evidence for a nonzero tunneling time delay and a nonvanishing longitudinal momentum of the electron at the “tunnel exit.”

Position based cryptography and multiparty communication complexity - Brody, Joshua; Dziembowski, Stefan; Faust, Sebastian; Pietrzak, Krzysztof Z
Position based cryptography (PBC), proposed in the seminal work of Chandran, Goyal, Moriarty, and Ostrovsky (SIAM J. Computing, 2014), aims at constructing cryptographic schemes in which the identity of the user is his geographic position. Chandran et al. construct PBC schemes for secure positioning and position-based key agreement in the bounded-storage model (Maurer, J. Cryptology, 1992). Apart from bounded memory, their security proofs need a strong additional restriction on the power of the adversary: he cannot compute joint functions of his inputs. Removing this assumption is left as an open problem. We show that an answer to this question would resolve a long standing open problem in multiparty communication complexity: finding a function that is hard to compute with low communication complexity in the simultaneous message model, but easy to compute in the fully adaptive model. On a more positive side: we also show some implications in the other direction, i.e.: we prove that lower bounds on the communication complexity of certain multiparty problems imply existence of PBC primitives. Using this result we then show two attractive ways to “bypass” our hardness result: the first uses the random oracle model, the second weakens the locality requirement in the bounded-storage model to online computability. The random oracle construction is arguably one of the simplest proposed so far in this area. Our results indicate that constructing improved provably secure protocols for PBC requires a better understanding of multiparty communication complexity. This is yet another example where negative results in one area (in our case: lower bounds in multiparty communication complexity) can be used to construct secure cryptographic schemes.

Molecular impurities interacting with a many-particle environment: From ultracold gases to helium nanodroplets - Lemeshko, Mikhail; Schmidt, Richard (Cold Chemistry: Molecular Scattering and Reactivity Near Absolute Zero)
In several settings of physics and chemistry one has to deal with molecules interacting with some kind of an external environment, be it a gas, a solution, or a crystal surface. Understanding molecular processes in the presence of such a many-particle bath is inherently challenging, and usually requires large-scale numerical computations. Here, we present an alternative approach to the problem, based on the notion of the angulon quasiparticle. We show that molecules rotating inside superfluid helium nanodroplets and Bose–Einstein condensates form angulons, and therefore can be described by straightforward solutions of a simple microscopic Hamiltonian. Casting the problem in the language of angulons allows us not only to greatly simplify it, but also to gain insights into the origins of the observed phenomena and to make predictions for future experimental studies.

Moderately hard functions: Definition, instantiations, and applications - Alwen, Joel F; Tackmann, Björn
Several cryptographic schemes and applications are based on functions that are both reasonably efficient to compute and moderately hard to invert, including client puzzles for Denial-of-Service protection, password protection via salted hashes, or recent proof-of-work blockchain systems. Despite their wide use, a definition of this concept has not yet been distilled and formalized explicitly. Instead, either the applications are proven directly based on the assumptions underlying the function, or some property of the function is proven, but the security of the application is argued only informally. The goal of this work is to provide a (universal) definition that decouples the efforts of designing new moderately hard functions and of building protocols based on them, serving as an interface between the two. On a technical level, beyond the mentioned definitions, we instantiate the model for four different notions of hardness. We extend the work of Alwen and Serbinenko (STOC 2015) by providing a general tool for proving security for the first notion of memory-hard functions that allows for provably secure applications. The tool allows us to recover all of the graph-theoretic techniques developed for proving security under the older, non-composable, notion of security used by Alwen and Serbinenko. As an application of our definition of moderately hard functions, we prove the security of two different schemes for proofs of effort (PoE). We also formalize and instantiate the concept of a non-interactive proof of effort (niPoE), in which the proof is not bound to a particular communication context but rather any bit-string chosen by the prover.

On generalized Heawood inequalities for manifolds: A van Kampen–Flores type nonembeddability result - Goaoc, Xavier; Mabillard, Isaac; Paták, Pavel; Patakova, Zuzana; Tancer, Martin; Wagner, Uli (Israel Journal of Mathematics)
The fact that the complete graph K5 does not embed in the plane has been generalized in two independent directions. On the one hand, the solution of the classical Heawood problem for graphs on surfaces established that the complete graph Kn embeds in a closed surface M (other than the Klein bottle) if and only if (n−3)(n−4) ≤ 6b1(M), where b1(M) is the first Z2-Betti number of M. On the other hand, van Kampen and Flores proved that the k-skeleton of the n-dimensional simplex (the higher-dimensional analogue of Kn+1) embeds in R2k if and only if n ≤ 2k + 1. Two decades ago, Kühnel conjectured that the k-skeleton of the n-simplex embeds in a compact, (k − 1)-connected 2k-manifold with kth Z2-Betti number bk only if the following generalized Heawood inequality holds: (k+1 n−k−1) ≤ (k+1 2k+1)bk. This is a common generalization of the case of graphs on surfaces as well as the van Kampen–Flores theorem. In the spirit of Kühnel’s conjecture, we prove that if the k-skeleton of the n-simplex embeds in a compact 2k-manifold with kth Z2-Betti number bk, then n ≤ 2bk(k 2k+2)+2k+4. This bound is weaker than the generalized Heawood inequality, but does not require the assumption that M is (k−1)-connected. Our results generalize to maps without q-covered points, in the spirit of Tverberg’s theorem, for q a prime power. Our proof uses a result of Volovikov about maps that satisfy a certain homological triviality condition.

Evolution of flower color pattern through selection on regulatory small RNAs - Bradley, Desmond; Xu, Ping; Mohorianu, Irina; Whibley, Annabel; Field, David; Tavares, Hugo; Couchman, Matthew; Copsey, Lucy; Carpenter, Rosemary; Li, Miaomiao; Li, Qun; Xue, Yongbiao; et al. (Science)
Small RNAs (sRNAs) regulate genes in plants and animals. Here, we show that population-wide differences in color patterns in snapdragon flowers are caused by an inverted duplication that generates sRNAs. The complexity and size of the transcripts indicate that the duplication represents an intermediate on the pathway to microRNA evolution. The sRNAs repress a pigment biosynthesis gene, creating a yellow highlight at the site of pollinator entry. The inverted duplication exhibits steep clines in allele frequency in a natural hybrid zone, showing that the allele is under selection. Thus, regulatory interactions of evolutionarily recent sRNAs can be acted upon by selection and contribute to the evolution of phenotypic diversity.

Shaping bacterial population behavior through computer interfaced control of individual cells - Chait, Remy P; Ruess, Jakob; Bergmiller, Tobias; Tkacik, Gasper; Guet, Calin C (Nature Communications)
Bacteria in groups vary individually, and interact with other bacteria and the environment to produce population-level patterns of gene expression. Investigating such behavior in detail requires measuring and controlling populations at the single-cell level alongside precisely specified interactions and environmental characteristics. Here we present an automated, programmable platform that combines image-based gene expression and growth measurements with on-line optogenetic expression control for hundreds of individual Escherichia coli cells over days, in a dynamically adjustable environment. This integrated platform broadly enables experiments that bridge individual and population behaviors. We demonstrate: (i) population structuring by independent closed-loop control of gene expression in many individual cells, (ii) cell-cell variation control during antibiotic perturbation, (iii) hybrid bio-digital circuits in single cells, and freely specifiable digital communication between individual bacteria. These examples showcase the potential for real-time integration of theoretical models with measurement and control of many individual cells to investigate and engineer microbial population behavior.

Universality for random matrix flows with time dependent density - Erdös, László; Schnelli, Kevin (Annales de l'institut Henri Poincare (B) Probability and Statistics)
We show that the Dyson Brownian Motion exhibits local universality after a very short time assuming that local rigidity and level repulsion of the eigenvalues hold. These conditions are verified, hence bulk spectral universality is proven, for a large class of Wigner-like matrices, including deformed Wigner ensembles and ensembles with non-stochastic variance matrices whose limiting densities differ from Wigner's semicircle law.

Extracerebral dysfunction in animal models of autism spectrum disorder - Hill Yardin, Elisa; Mckeown, Sonja; Novarino, Gaia; Grabrucker, Andreas (Translational Anatomy and Cell Biology of Autism Spectrum Disorder)
Genetic factors might be largely responsible for the development of autism spectrum disorder (ASD) that alone or in combination with specific environmental risk factors trigger the pathology. Multiple mutations identified in ASD patients that impair synaptic function in the central nervous system are well studied in animal models. How these mutations might interact with other risk factors is not fully understood though. Additionally, how systems outside of the brain are altered in the context of ASD is an emerging area of research. Extracerebral influences on the physiology could begin in utero and contribute to changes in the brain and in the development of other body systems and further lead to epigenetic changes. Therefore, multiple recent studies have aimed at elucidating the role of gene-environment interactions in ASD. Here we provide an overview on the extracerebral systems that might play an important associative role in ASD and review evidence regarding the potential roles of inflammation, trace metals, metabolism, genetic susceptibility, enteric nervous system function and the microbiota of the gastrointestinal (GI) tract on the development of endophenotypes in animal models of ASD. By influencing environmental conditions, it might be possible to reduce or limit the severity of ASD pathology.

The infinitesimal model: Definition derivation and implications - Barton, Nicholas H; Etheridge, Alison; Véber, Amandine (Theoretical Population Biology)
Our focus here is on the infinitesimal model. In this model, one or several quantitative traits are described as the sum of a genetic and a non-genetic component, the first being distributed within families as a normal random variable centred at the average of the parental genetic components, and with a variance independent of the parental traits. Thus, the variance that segregates within families is not perturbed by selection, and can be predicted from the variance components. This does not necessarily imply that the trait distribution across the whole population should be Gaussian, and indeed selection or population structure may have a substantial effect on the overall trait distribution. One of our main aims is to identify some general conditions on the allelic effects for the infinitesimal model to be accurate. We first review the long history of the infinitesimal model in quantitative genetics. Then we formulate the model at the phenotypic level in terms of individual trait values and relationships between individuals, but including different evolutionary processes: genetic drift, recombination, selection, mutation, population structure, …. We give a range of examples of its application to evolutionary questions related to stabilising selection, assortative mating, effective population size and response to selection, habitat preference and speciation. We provide a mathematical justification of the model as the limit as the number M of underlying loci tends to infinity of a model with Mendelian inheritance, mutation and environmental noise, when the genetic component of the trait is purely additive. We also show how the model generalises to include epistatic effects. We prove in particular that, within each family, the genetic components of the individual trait values in the current generation are indeed normally distributed with a variance independent of ancestral traits, up to an error of order 1∕M. Simulations suggest that in some cases the convergence may be as fast as 1∕M.

The cost of exactness in quantitative reachability - Chatterjee, Krishnendu; Doyen, Laurent; Henzinger, Thomas A (Models, Algorithms, Logics and Tools)
In the analysis of reactive systems a quantitative objective assigns a real value to every trace of the system. The value decision problem for a quantitative objective requires a trace whose value is at least a given threshold, and the exact value decision problem requires a trace whose value is exactly the threshold. We compare the computational complexity of the value and exact value decision problems for classical quantitative objectives, such as sum, discounted sum, energy, and mean-payoff for two standard models of reactive systems, namely, graphs and graph games.

MazF activation promotes translational heterogeneity of the grcA mRNA in Escherichia coli populations - Nikolic, Nela; Didara, Zrinka; Moll, Isabella (PeerJ)
Bacteria adapt to adverse environmental conditions by altering gene expression patterns. Recently, a novel stress adaptation mechanism has been described that allows Escherichia coli to alter gene expression at the post-transcriptional level. The key player in this regulatory pathway is the endoribonuclease MazF, the toxin component of the toxin-antitoxin module mazEF that is triggered by various stressful conditions. In general, MazF degrades the majority of transcripts by cleaving at ACA sites, which results in the retardation of bacterial growth. Furthermore, MazF can process a small subset of mRNAs and render them leaderless by removing their ribosome binding site. MazF concomitantly modifies ribosomes, making them selective for the translation of leaderless mRNAs. In this study, we employed fluorescent reporter-systems to investigate mazEF expression during stressful conditions, and to infer consequences of the mRNA processing mediated by MazF on gene expression at the single-cell level. Our results suggest that mazEF transcription is maintained at low levels in single cells encountering adverse conditions, such as antibiotic stress or amino acid starvation. Moreover, using the grcA mRNA as a model for MazF-mediated mRNA processing, we found that MazF activation promotes heterogeneity in the grcA reporter expression, resulting in a subpopulation of cells with increased levels of GrcA reporter protein.

Automated recurrence analysis for almost linear expected runtime bounds - Chatterjee, Krishnendu; Fu, Hongfei; Murhekar, Aniket
We consider the problem of developing automated techniques for solving recurrence relations to aid the expected-runtime analysis of programs. The motivation is that several classical textbook algorithms have quite efficient expected-runtime complexity, whereas the corresponding worst-case bounds are either inefficient (e.g., Quick-Sort), or completely ineffective (e.g., Coupon-Collector). Since the main focus of expected-runtime analysis is to obtain efficient bounds, we consider bounds that are either logarithmic, linear or almost-linear (O(log n), O(n), O(n · log n), respectively, where n represents the input size). Our main contribution is an efficient (simple linear-time algorithm) sound approach for deriving such expected-runtime bounds for the analysis of recurrence relations induced by randomized algorithms. The experimental results show that our approach can efficiently derive asymptotically optimal expected-runtime bounds for recurrences of classical randomized algorithms, including Randomized-Search, Quick-Sort, Quick-Select, Coupon-Collector, where the worst-case bounds are either inefficient (such as linear as compared to logarithmic expected-runtime complexity, or quadratic as compared to linear or almost-linear expected-runtime complexity), or ineffective.

Reconstitution of protein dynamics involved in bacterial cell division - Loose, Martin; Zieske, Katja; Schwille, Petra (Prokaryotic Cytoskeletons)
Even simple cells like bacteria have precisely regulated cellular anatomies, which allow them to grow, divide and to respond to internal or external cues with high fidelity. How spatial and temporal intracellular organization in prokaryotic cells is achieved and maintained on the basis of locally interacting proteins still remains largely a mystery. Bulk biochemical assays with purified components and in vivo experiments help us to approach key cellular processes from two opposite ends, in terms of minimal and maximal complexity. However, to understand how cellular phenomena emerge, that are more than the sum of their parts, we have to assemble cellular subsystems step by step from the bottom up. Here, we review recent in vitro reconstitution experiments with proteins of the bacterial cell division machinery and illustrate how they help to shed light on fundamental cellular mechanisms that constitute spatiotemporal order and regulate cell division.

Biosignals standards and FHIR: The way to go - Sauermann, Stefan; David, Veronika; Schlögl, Alois; Egelkraut, Reinhard; Frohner, Matthias; Pohn, Birgit; Urbauer, Philipp; Mense, Alexander
Background: Standards have become available to share semantically encoded vital parameters from medical devices, as required for example by personal healthcare records. Standardised sharing of biosignal data largely remains open. Objectives: The goal of this work is to explore available biosignal file format and data exchange standards and profiles, and to conceptualise end-To-end solutions. Methods: The authors reviewed and discussed available biosignal file format standards with other members of international standards development organisations (SDOs). Results: A raw concept for standards based acquisition, storage, archiving and sharing of biosignals was developed. The GDF format may serve for storing biosignals. Signals can then be shared using FHIR resources and may be stored on FHIR servers or in DICOM archives, with DICOM waveforms as one possible format. Conclusion: Currently a group of international SDOs (e.g. HL7, IHE, DICOM, IEEE) is engaged in intensive discussions. This discussion extends existing work that already was adopted by large implementer communities. The concept presented here only reports the current status of the discussion in Austria. The discussion will continue internationally, with results to be expected over the coming years.

A note on 2D focusing many boson systems - Lewin, Mathieu; Nam, Phan; Rougerie, Nicolas (Proceedings of the American Mathematical Society)
We consider a 2D quantum system of N bosons in a trapping potential |x|s, interacting via a pair potential of the form N2β−1 w(Nβ x). We show that for all 0 < β < (s + 1)/(s + 2), the leading order behavior of ground states of the many-body system is described in the large N limit by the corresponding cubic nonlinear Schrödinger energy functional. Our result covers the focusing case (w < 0) where even the stability of the many-body system is not obvious. This answers an open question mentioned by X. Chen and J. Holmer for harmonic traps (s = 2). Together with the BBGKY hierarchy approach used by these authors, our result implies the convergence of the many-body quantum dynamics to the focusing NLS equation with harmonic trap for all 0 < β < 3/4.

Genetic and pharmacological reversibility of phenotypes in mouse models of autism spectrum disorder - Schroeder, Jan; Deliu, Elena; Novarino, Gaia; Schmeisser, Michael (Translational Anatomy and Cell Biology of Autism Spectrum Disorder)
As autism spectrum disorder (ASD) is largely regarded as a neurodevelopmental condition, long-time consensus was that its hallmark features are irreversible. However, several studies from recent years using defined mouse models of ASD have provided clear evidence that in mice neurobiological and behavioural alterations can be ameliorated or even reversed by genetic restoration or pharmacological treatment either before or after symptom onset. Here, we review findings on genetic and pharmacological reversibility of phenotypes in mouse models of ASD. Our review should give a comprehensive overview on both aspects and encourage future studies to better understand the underlying molecular mechanisms that might be translatable from animals to humans.

Challenges and tool implementation of hybrid rapidly exploring random trees - Bak, Stanley; Bogomolov, Sergiy; Henzinger, Thomas A; Kumar, Aviral
A Rapidly-exploring Random Tree (RRT) is an algorithm which can search a non-convex region of space by incrementally building a space-filling tree. The tree is constructed from random points drawn from system’s state space and is biased to grow towards large unexplored areas in the system. RRT can provide better coverage of a system’s possible behaviors compared with random simulations, but is more lightweight than full reachability analysis. In this paper, we explore some of the design decisions encountered while implementing a hybrid extension of the RRT algorithm, which have not been elaborated on before. In particular, we focus on handling non-determinism, which arises due to discrete transitions. We introduce the notion of important points to account for this phenomena. We showcase our ideas using heater and navigation benchmarks.

Scrypt is maximally memory hard - Alwen, Joel F; Chen, Binchi; Pietrzak, Krzysztof Z; Reyzin, Leonid; Tessaro, Stefano
Memory-hard functions (MHFs) are hash algorithms whose evaluation cost is dominated by memory cost. As memory, unlike computation, costs about the same across different platforms, MHFs cannot be evaluated at significantly lower cost on dedicated hardware like ASICs. MHFs have found widespread applications including password hashing, key derivation, and proofs-of-work. This paper focuses on scrypt, a simple candidate MHF designed by Percival, and described in RFC 7914. It has been used within a number of cryptocurrencies (e.g., Litecoin and Dogecoin) and has been an inspiration for Argon2d, one of the winners of the recent password-hashing competition. Despite its popularity, no rigorous lower bounds on its memory complexity are known. We prove that scrypt is optimally memory-hard, i.e., its cumulative memory complexity (cmc) in the parallel random oracle model is Ω(n2w), where w and n are the output length and number of invocations of the underlying hash function, respectively. High cmc is a strong security target for MHFs introduced by Alwen and Serbinenko (STOC’15) which implies high memory cost even for adversaries who can amortize the cost over many evaluations and evaluate the underlying hash functions many times in parallel. Our proof is the first showing optimal memory-hardness for any MHF. Our result improves both quantitatively and qualitatively upon the recent work by Alwen et al. (EUROCRYPT’16) who proved a weaker lower bound of Ω(n2w/ log2 n) for a restricted class of adversaries.

On the quantitative semantics of regular expressions over real-valued signals - Bakhirkin, Alexey; Ferrere, Thomas; Maler, Oded; Ulus, Dogan
Signal regular expressions can specify sequential properties of real-valued signals based on threshold conditions, regular operations, and duration constraints. In this paper we endow them with a quantitative semantics which indicates how robustly a signal matches or does not match a given expression. First, we show that this semantics is a safe approximation of a distance between the signal and the language defined by the expression. Then, we consider the robust matching problem, that is, computing the quantitative semantics of every segment of a given signal relative to an expression. We present an algorithm that solves this problem for piecewise-constant and piecewise-linear signals and show that for such signals the robustness map is a piecewise-linear function. The availability of an indicator describing how robustly a signal segment matches some regular pattern provides a general framework for quantitative monitoring of cyber-physical systems.

Numerical Software Verification
This book constitutes the refereed proceedings of the 9th InternationalWorkshop on Numerical Software Verification, NSV 2016, held in Toronto, ON, Canada in July 2011 - colocated with CAV 2016, the 28th International Conference on Computer Aided Verification. The NSV workshop is dedicated to the development of logical and mathematical techniques for the reasoning about programmability and reliability.

Depth-robust graphs and their cumulative memory complexity - Alwen, Joel F; Blocki, Jeremiah; Pietrzak, Krzysztof Z
Data-independent Memory Hard Functions (iMHFS) are finding a growing number of applications in security; especially in the domain of password hashing. An important property of a concrete iMHF is specified by fixing a directed acyclic graph (DAG) Gn on n nodes. The quality of that iMHF is then captured by the following two pebbling complexities of Gn: – The parallel cumulative pebbling complexity Π∥cc(Gn) must be as high as possible (to ensure that the amortized cost of computing the function on dedicated hardware is dominated by the cost of memory). – The sequential space-time pebbling complexity Πst(Gn) should be as close as possible to Π∥cc(Gn) (to ensure that using many cores in parallel and amortizing over many instances does not give much of an advantage). In this paper we construct a family of DAGs with best possible parameters in an asymptotic sense, i.e., where Π∥cc(Gn) = Ω(n2/ log(n)) (which matches a known upper bound) and Πst(Gn) is within a constant factor of Π∥cc(Gn). Our analysis relies on a new connection between the pebbling complexity of a DAG and its depth-robustness (DR) – a well studied combinatorial property. We show that high DR is sufficient for high Π∥cc. Alwen and Blocki (CRYPTO’16) showed that high DR is necessary and so, together, these results fully characterize DAGs with high Π∥cc in terms of DR. Complementing these results, we provide new upper and lower bounds on the Π∥cc of several important candidate iMHFs from the literature. We give the first lower bounds on the memory hardness of the Catena and Balloon Hashing functions in a parallel model of computation and we give the first lower bounds of any kind for (a version) of Argon2i. Finally we describe a new class of pebbling attacks improving on those of Alwen and Blocki (CRYPTO’16). By instantiating these attacks we upperbound the Π∥cc of the Password Hashing Competition winner Argon2i and one of the Balloon Hashing functions by O (n1.71). We also show an upper bound of O(n1.625) for the Catena functions and the two remaining Balloon Hashing functions.

Graphical model parameter learning by inverse linear programming - Trajkovska, Vera; Swoboda, Paul; Åström, Freddie; Petra, Stefanie
We introduce two novel methods for learning parameters of graphical models for image labelling. The following two tasks underline both methods: (i) perturb model parameters based on given features and ground truth labelings, so as to exactly reproduce these labelings as optima of the local polytope relaxation of the labelling problem; (ii) train a predictor for the perturbed model parameters so that improved model parameters can be applied to the labelling of novel data. Our first method implements task (i) by inverse linear programming and task (ii) using a regressor e.g. a Gaussian process. Our second approach simultaneously solves tasks (i) and (ii) in a joint manner, while being restricted to linearly parameterised predictors. Experiments demonstrate the merits of both approaches.

Synchronizing the asynchronous - Henzinger, Thomas A; Kragl, Bernhard; Qadeer, Shaz
Synchronous programs are easy to specify because the side effects of an operation are finished by the time the invocation of the operation returns to the caller. Asynchronous programs, on the other hand, are difficult to specify because there are side effects due to pending computation scheduled as a result of the invocation of an operation. They are also difficult to verify because of the large number of possible interleavings of concurrent asynchronous computation threads. We show that specifications and correctness proofs for asynchronous programs can be structured by introducing the fiction, for proof purposes, that intermediate, non-quiescent states of asynchronous operations can be ignored. Then, the task of specification becomes relatively simple and the task of verification can be naturally decomposed into smaller sub-tasks. The sub-tasks iteratively summarize, guided by the structure of an asynchronous program, the atomic effect of non-atomic operations and the synchronous effect of asynchronous operations. This structuring of specifications and proofs corresponds to the introduction of multiple layers of stepwise refinement for asynchronous programs. We present the first proof rule, called synchronization, to reduce asynchronous invocations on a lower layer to synchronous invocations on a higher layer. We implemented our proof method in CIVL and evaluated it on a collection of benchmark programs.

Effects of B vitamins overload on plasma insulin level and hydrogen peroxide generation in rats - Sun, Wuping; Zhai, Ming-Zhu; Zhou, Qian; Qian, Chengrui; Jiang, Changyu (Chinese Journal of Physiology)
It has been reported that nicotinamide-overload induces oxidative stress associated with insulin resistance, the key feature of type 2 diabetes mellitus (T2DM). This study aimed to investigate the effects of B vitamins in T2DM. Glucose tolerance tests (GTT) were carried out in adult Sprague-Dawley rats treated with or without cumulative doses of B vitamins. More specifically, insulin tolerance tests (ITT) were also carried out in adult Sprague-Dawley rats treated with or without cumulative doses of Vitamin B3. We found that cumulative Vitamin B1 and Vitamin B3 administration significantly increased the plasma H2O2 levels associated with high insulin levels. Only Vitamin B3 reduced muscular and hepatic glycogen contents. Cumulative administration of nicotinic acid, another form of Vitamin B3, also significantly increased plasma insulin level and H2O2 generation. Moreover, cumulative administration of nicotinic acid or nicotinamide impaired glucose metabolism. This study suggested that excess Vitamin B1 and Vitamin B3 caused oxidative stress and insulin resistance.

Localization errors in solving stochastic partial differential equations in the whole space - Gerencser, Mate; Gyöngy, István (Mathematics of Computation)
Cauchy problems with SPDEs on the whole space are localized to Cauchy problems on a ball of radius R. This localization reduces various kinds of spatial approximation schemes to finite dimensional problems. The error is shown to be exponentially small. As an application, a numerical scheme is presented which combines the localization and the space and time discretization, and thus is fully implementable.

Value iteration for long run average reward in markov decision processes - Ashok, Pranav; Chatterjee, Krishnendu; Daca, Przemyslaw; Kretinsky, Jan; Meggendorfer, Tobias
Markov decision processes (MDPs) are standard models for probabilistic systems with non-deterministic behaviours. Long-run average rewards provide a mathematically elegant formalism for expressing long term performance. Value iteration (VI) is one of the simplest and most efficient algorithmic approaches to MDPs with other properties, such as reachability objectives. Unfortunately, a naive extension of VI does not work for MDPs with long-run average rewards, as there is no known stopping criterion. In this work our contributions are threefold. (1) We refute a conjecture related to stopping criteria for MDPs with long-run average rewards. (2) We present two practical algorithms for MDPs with long-run average rewards based on VI. First, we show that a combination of applying VI locally for each maximal end-component (MEC) and VI for reachability objectives can provide approximation guarantees. Second, extending the above approach with a simulation-guided on-demand variant of VI, we present an anytime algorithm that is able to deal with very large models. (3) Finally, we present experimental results showing that our methods significantly outperform the standard approaches on several benchmarks.

The complexity of general-valued CSPs - Kolmogorov, Vladimir; Krokhin, Andrei; Rolinek, Michal (SIAM Journal on Computing)
An instance of the valued constraint satisfaction problem (VCSP) is given by a finite set of variables, a finite domain of labels, and a sum of functions, each function depending on a subset of the variables. Each function can take finite values specifying costs of assignments of labels to its variables or the infinite value, which indicates an infeasible assignment. The goal is to find an assignment of labels to the variables that minimizes the sum. We study, assuming that P 6= NP, how the complexity of this very general problem depends on the set of functions allowed in the instances, the so-called constraint language. The case when all allowed functions take values in f0;1g corresponds to ordinary CSPs, where one deals only with the feasibility issue, and there is no optimization. This case is the subject of the algebraic CSP dichotomy conjecture predicting for which constraint languages CSPs are tractable (i.e., solvable in polynomial time) and for which they are NP-hard. The case when all allowed functions take only finite values corresponds to a finitevalued CSP, where the feasibility aspect is trivial and one deals only with the optimization issue. The complexity of finite-valued CSPs was fully classified by Thapper and Živný. An algebraic necessary condition for tractability of a general-valued CSP with a fixed constraint language was recently given by Kozik and Ochremiak. As our main result, we prove that if a constraint language satisfies this algebraic necessary condition, and the feasibility CSP (i.e., the problem of deciding whether a given instance has a feasible solution) corresponding to the VCSP with this language is tractable, then the VCSP is tractable. The algorithm is a simple combination of the assumed algorithm for the feasibility CSP and the standard LP relaxation. As a corollary, we obtain that a dichotomy for ordinary CSPs would imply a dichotomy for general-valued CSPs.

A novel convex relaxation for non binary discrete tomography - Kuske, Jan; Swoboda, Paul; Petra, Stefanie
We present a novel convex relaxation and a corresponding inference algorithm for the non-binary discrete tomography problem, that is, reconstructing discrete-valued images from few linear measurements. In contrast to state of the art approaches that split the problem into a continuous reconstruction problem for the linear measurement constraints and a discrete labeling problem to enforce discrete-valued reconstructions, we propose a joint formulation that addresses both problems simultaneously, resulting in a tighter convex relaxation. For this purpose a constrained graphical model is set up and evaluated using a novel relaxation optimized by dual decomposition. We evaluate our approach experimentally and show superior solutions both mathematically (tighter relaxation) and experimentally in comparison to previously proposed relaxations.

On the complexity of breaking pseudoentropy - Skórski, Maciej
Pseudoentropy has found a lot of important applications to cryptography and complexity theory. In this paper we focus on the foundational problem that has not been investigated so far, namely by how much pseudoentropy (the amount seen by computationally bounded attackers) diﬀers from its information-theoretic counterpart (seen by unbounded observers), given certain limits on attacker’s computational power? We provide the following answer for HILL pseudoentropy, which exhibits a threshold behavior around the size exponential in the entropy amount:– If the attacker size (s) and advantage () satisfy s (formula presented) where k is the claimed amount of pseudoentropy, then the pseudoentropy boils down to the information-theoretic smooth entropy. – If s (formula presented) then pseudoentropy could be arbitrarily bigger than the information-theoretic smooth entropy. Besides answering the posted question, we show an elegant application of our result to the complexity theory, namely that it implies the clas-sical result on the existence of functions hard to approximate (due to Pippenger). In our approach we utilize non-constructive techniques: the duality of linear programming and the probabilistic method.

Entropic Ricci curvature for discrete spaces - Maas, Jan (Modern Approaches to Discrete Curvature)
We give a short overview on a recently developed notion of Ricci curvature for discrete spaces. This notion relies on geodesic convexity properties of the relative entropy along geodesics in the space of probability densities, for a metric which is similar to (but different from) the 2-Wasserstein metric. The theory can be considered as a discrete counterpart to the theory of Ricci curvature for geodesic measure spaces developed by Lott–Sturm–Villani.

A cryptographic view of regularity lemmas: Simpler unified proofs and refined bounds - Skórski, Maciej
In this work we present a short and unified proof for the Strong and Weak Regularity Lemma, based on the cryptographic tech-nique called low-complexity approximations. In short, both problems reduce to a task of finding constructively an approximation for a certain target function under a class of distinguishers (test functions), where dis-tinguishers are combinations of simple rectangle-indicators. In our case these approximations can be learned by a simple iterative procedure, which yields a unified and simple proof, achieving for any graph with density d and any approximation parameter the partition size. The novelty in our proof is: (a) a simple approach which yields both strong and weaker variant, and (b) improvements when d = o(1). At an abstract level, our proof can be seen a refinement and simplification of the “analytic” proof given by Lovasz and Szegedy.

Improved set-based symbolic algorithms for parity games - Chatterjee, Krishnendu; Dvorák, Wolfgang; Henzinger, Monika H; Loitzenbauer, Veronika
Graph games with omega-regular winning conditions provide a mathematical framework to analyze a wide range of problems in the analysis of reactive systems and programs (such as the synthesis of reactive systems, program repair, and the verification of branching time properties). Parity conditions are canonical forms to specify omega-regular winning conditions. Graph games with parity conditions are equivalent to mu-calculus model checking, and thus a very important algorithmic problem. Symbolic algorithms are of great significance because they provide scalable algorithms for the analysis of large finite-state systems, as well as algorithms for the analysis of infinite-state systems with finite quotient. A set-based symbolic algorithm uses the basic set operations and the one-step predecessor operators. We consider graph games with n vertices and parity conditions with c priorities (equivalently, a mu-calculus formula with c alternations of least and greatest fixed points). While many explicit algorithms exist for graph games with parity conditions, for set-based symbolic algorithms there are only two algorithms (notice that we use space to refer to the number of sets stored by a symbolic algorithm): (a) the basic algorithm that requires O(n^c) symbolic operations and linear space; and (b) an improved algorithm that requires O(n^{c/2+1}) symbolic operations but also O(n^{c/2+1}) space (i.e., exponential space). In this work we present two set-based symbolic algorithms for parity games: (a) our first algorithm requires O(n^{c/2+1}) symbolic operations and only requires linear space; and (b) developing on our first algorithm, we present an algorithm that requires O(n^{c/3+1}) symbolic operations and only linear space. We also present the first linear space set-based symbolic algorithm for parity games that requires at most a sub-exponential number of symbolic operations.

Embedding graphs into embedded graphs - Fulek, Radoslav
A (possibly degenerate) drawing of a graph G in the plane is approximable by an embedding if it can be turned into an embedding by an arbitrarily small perturbation. We show that testing, whether a drawing of a planar graph G in the plane is approximable by an embedding, can be carried out in polynomial time, if a desired embedding of G belongs to a fixed isotopy class, i.e., the rotation system (or equivalently the faces) of the embedding of G and the choice of outer face are fixed. In other words, we show that c-planarity with embedded pipes is tractable for graphs with fixed embeddings. To the best of our knowledge an analogous result was previously known essentially only when G is a cycle.

Dynamical self consistency leads to behavioral development and emergent social interactions in robots - Der, Ralf; Martius, Georg S
We present an approach that enables robots to self-organize their sensorimotor behavior from scratch without providing specific information about neither the robot nor its environment. This is achieved by a simple neural control law that increases the consistency between external sensor dynamics and internal neural dynamics of the utterly simple controller. In this way, the embodiment and the agent-environment coupling are the only source of individual development. We show how an anthropomorphic tendon driven arm-shoulder system develops different behaviors depending on that coupling. For instance: Given a bottle half-filled with water, the arm starts to shake it, driven by the physical response of the water. When attaching a brush, the arm can be manipulated into wiping a table, and when connected to a revolvable wheel it finds out how to rotate it. Thus, the robot may be said to discover the affordances of the world. When allowing two (simulated) humanoid robots to interact physically, they engage into a joint behavior development leading to, for instance, spontaneous cooperation. More social effects are observed if the robots can visually perceive each other. Although, as an observer, it is tempting to attribute an apparent intentionality, there is nothing of the kind put in. As a conclusion, we argue that emergent behavior may be much less rooted in explicit intentions, internal motivations, or specific reward systems than is commonly believed.

Fluid dynamics: Water flows out of touch - Hof, Björn (Nature)
Superhydrophobic surfaces reduce the frictional drag between water and solid materials, but this effect is often temporary. The realization of sustained drag reduction has applications for water vehicles and pipeline flows.

Limited heterogeneity of known driver gene mutations among the metastases of individual patients with pancreatic cancer - Makohon Moore, Alvin; Zhang, Ming; Reiter, Johannes; Božić, Ivana; Allen, Benjamin; Kundu, Deepanjan; Chatterjee, Krishnendu; Wong, Fay; Jiao, Yuchen; Kohutek, Zachary; Hong, Jungeui; Attiyeh, Marc; et al. (Nature Genetics)
The extent of heterogeneity among driver gene mutations present in naturally occurring metastases - that is, treatment-naive metastatic disease - is largely unknown. To address this issue, we carried out 60× whole-genome sequencing of 26 metastases from four patients with pancreatic cancer. We found that identical mutations in known driver genes were present in every metastatic lesion for each patient studied. Passenger gene mutations, which do not have known or predicted functional consequences, accounted for all intratumoral heterogeneity. Even with respect to these passenger mutations, our analysis suggests that the genetic similarity among the founding cells of metastases was higher than that expected for any two cells randomly taken from a normal tissue. The uniformity of known driver gene mutations among metastases in the same patient has critical and encouraging implications for the success of future targeted therapies in advanced-stage disease.

Practical graphs for optimal side-channel resistant memory-hard functions - Alwen, Joel F; Blocki, Jeremiah; Harsha, Ben (Proceedings of the 2017 ACM SIGSAC Conference on Computer and Communications Security)
A memory-hard function (MHF) ƒn with parameter n can be computed in sequential time and space n. Simultaneously, a high amortized parallel area-time complexity (aAT) is incurred per evaluation. In practice, MHFs are used to limit the rate at which an adversary (using a custom computational device) can evaluate a security sensitive function that still occasionally needs to be evaluated by honest users (using an off-the-shelf general purpose device). The most prevalent examples of such sensitive functions are Key Derivation Functions (KDFs) and password hashing algorithms where rate limits help mitigate off-line dictionary attacks. As the honest users' inputs to these functions are often (low-entropy) passwords special attention is given to a class of side-channel resistant MHFs called iMHFs. Essentially all iMHFs can be viewed as some mode of operation (making n calls to some round function) given by a directed acyclic graph (DAG) with very low indegree. Recently, a combinatorial property of a DAG has been identified (called "depth-robustness") which results in good provable security for an iMHF based on that DAG. Depth-robust DAGs have also proven useful in other cryptographic applications. Unfortunately, up till now, all known very depth-robust DAGs are impractically complicated and little is known about their exact (i.e. non-asymptotic) depth-robustness both in theory and in practice. In this work we build and analyze (both formally and empirically) several exceedingly simple and efficient to navigate practical DAGs for use in iMHFs and other applications. For each DAG we: *Prove that their depth-robustness is asymptotically maximal. *Prove bounds of at least 3 orders of magnitude better on their exact depth-robustness compared to known bounds for other practical iMHF. *Implement and empirically evaluate their depth-robustness and aAT against a variety of state-of-the art (and several new) depth-reduction and low aAT attacks. We find that, against all attacks, the new DAGs perform significantly better in practice than Argon2i, the most widely deployed iMHF in practice. Along the way we also improve the best known empirical attacks on the aAT of Argon2i by implementing and testing several heuristic versions of a (hitherto purely theoretical) depth-reduction attack. Finally, we demonstrate practicality of our constructions by modifying the Argon2i code base to use one of the new high aAT DAGs. Experimental benchmarks on a standard off-the-shelf CPU show that the new modifications do not adversely affect the impressive throughput of Argon2i (despite seemingly enjoying significantly higher aAT).

Creating to understand – developmental biology meets engineering in Paris - Kicheva, Anna; Rivron, Nicolas (Development)
In November 2016, developmental biologists, synthetic biologists and engineers gathered in Paris for a meeting called ‘Engineering the embryo’. The participants shared an interest in exploring how synthetic systems can reveal new principles of embryonic development, and how the in vitro manipulation and modeling of development using stem cells can be used to integrate ideas and expertise from physics, developmental biology and tissue engineering. As we review here, the conference pinpointed some of the challenges arising at the intersection of these fields, along with great enthusiasm for finding new approaches and collaborations.

On the complexity of estimating Rènyi divergences - Skórski, Maciej (2017 IEEE International Symposium on Information Theory (ISIT))
This paper studies the complexity of estimating Rényi divergences of discrete distributions: p observed from samples and the baseline distribution q known a priori. Extending the results of Acharya et al. (SODA'15) on estimating Rényi entropy, we present improved estimation techniques together with upper and lower bounds on the sample complexity. We show that, contrarily to estimating Rényi entropy where a sublinear (in the alphabet size) number of samples suffices, the sample complexity is heavily dependent on events occurring unlikely in q, and is unbounded in general (no matter what an estimation technique is used). For any divergence of integer order bigger than 1, we provide upper and lower bounds on the number of samples dependent on probabilities of p and q (the lower bounds hold for non-integer orders as well). We conclude that the worst-case sample complexity is polynomial in the alphabet size if and only if the probabilities of q are non-negligible. This gives theoretical insights into heuristics used in the applied literature to handle numerical instability, which occurs for small probabilities of q. Our result shows that they should be handled with care not only because of numerical issues, but also because of a blow up in the sample complexity.

Bacterial flagella grow through an injection diffusion mechanism - Renault, Thibaud; Abraham, Anthony; Bergmiller, Tobias; Paradis, Guillaume; Rainville, Simon; Charpentier, Emmanuelle; Guet, Calin C; Tu, Yuhai; Namba, Keiichi; Keener, James; Minamino, Tohru; Erhardt, Marc (eLife)
The bacterial flagellum is a self-assembling nanomachine. The external flagellar filament, several times longer than a bacterial cell body, is made of a few tens of thousands subunits of a single protein: flagellin. A fundamental problem concerns the molecular mechanism of how the flagellum grows outside the cell, where no discernible energy source is available. Here, we monitored the dynamic assembly of individual flagella using in situ labelling and real-time immunostaining of elongating flagellar filaments. We report that the rate of flagellum growth, initially ~1,700 amino acids per second, decreases with length and that the previously proposed chain mechanism does not contribute to the filament elongation dynamics. Inhibition of the proton motive force-dependent export apparatus revealed a major contribution of substrate injection in driving filament elongation. The combination of experimental and mathematical evidence demonstrates that a simple, injection-diffusion mechanism controls bacterial flagella growth outside the cell.

Auxin response cell autonomously controls ground tissue initiation in the early arabidopsis embryo - Möller, Barbara; Ten Hove, Colette; Xiang, Daoquan; Williams, Nerys; López, Lorena; Yoshida, Saiko; Smit, Margot; Datla, Raju; Weijers, Dolf (PNAS)
Plant organs are typically organized into three main tissue layers. The middle ground tissue layer comprises the majority of the plant body and serves a wide range of functions, including photosynthesis, selective nutrient uptake and storage, and gravity sensing. Ground tissue patterning and maintenance in Arabidopsis are controlled by a well-established gene network revolving around the key regulator SHORT-ROOT (SHR). In contrast, it is completely unknown how ground tissue identity is first specified from totipotent precursor cells in the embryo. The plant signaling molecule auxin, acting through AUXIN RESPONSE FACTOR (ARF) transcription factors, is critical for embryo patterning. The auxin effector ARF5/MONOPTEROS (MP) acts both cell-autonomously and noncell-autonomously to control embryonic vascular tissue formation and root initiation, respectively. Here we show that auxin response and ARF activity cell-autonomously control the asymmetric division of the first ground tissue cells. By identifying embryonic target genes, we show that MP transcriptionally initiates the ground tissue lineage and acts upstream of the regulatory network that controls ground tissue patterning and maintenance. Strikingly, whereas the SHR network depends on MP, this MP function is, at least in part, SHR independent. Our study therefore identifies auxin response as a regulator of ground tissue specification in the embryonic root, and reveals that ground tissue initiation and maintenance use different regulators and mechanisms. Moreover, our data provide a framework for the simultaneous formation of multiple cell types by the same transcriptional regulator.

Modeling Alzheimer's disease in mice with human neurons - Novarino, Gaia (Science Translational Medicine)
Human neurons transplanted into a mouse model for Alzheimer’s disease show human-specific vulnerability to β-amyloid plaques and may help to identify new therapeutic targets.

Self organized behavior generation for musculoskeletal robots - Der, Ralf; Martius, Georg S (Frontiers in Neurorobotics)
With the accelerated development of robot technologies, control becomes one of the central themes of research. In traditional approaches, the controller, by its internal functionality, finds appropriate actions on the basis of specific objectives for the task at hand. While very successful in many applications, self-organized control schemes seem to be favored in large complex systems with unknown dynamics or which are difficult to model. Reasons are the expected scalability, robustness, and resilience of self-organizing systems. The paper presents a self-learning neurocontroller based on extrinsic differential plasticity introduced recently, applying it to an anthropomorphic musculoskeletal robot arm with attached objects of unknown physical dynamics. The central finding of the paper is the following effect: by the mere feedback through the internal dynamics of the object, the robot is learning to relate each of the objects with a very specific sensorimotor pattern. Specifically, an attached pendulum pilots the arm into a circular motion, a half-filled bottle produces axis oriented shaking behavior, a wheel is getting rotated, and wiping patterns emerge automatically in a table-plus-brush setting. By these object-specific dynamical patterns, the robot may be said to recognize the object's identity, or in other words, it discovers dynamical affordances of objects. Furthermore, when including hand coordinates obtained from a camera, a dedicated hand-eye coordination self-organizes spontaneously. These phenomena are discussed from a specific dynamical system perspective. Central is the dedicated working regime at the border to instability with its potentially infinite reservoir of (limit cycle) attractors "waiting" to be excited. Besides converging toward one of these attractors, variate behavior is also arising from a self-induced attractor morphing driven by the learning rule. We claim that experimental investigations with this anthropomorphic, self-learning robot not only generate interesting and potentially useful behaviors, but may also help to better understand what subjective human muscle feelings are, how they can be rooted in sensorimotor patterns, and how these concepts may feed back on robotics.

FMNL formins boost lamellipodial force generation - Kage, Frieda; Winterhoff, Moritz; Dimchev, Vanessa; Müller, Jan; Thalheim, Tobias; Freise, Anika; Brühmann, Stefan; Kollasser, Jana; Block, Jennifer; Dimchev, Georgi A; Geyer, Matthias; Schnittler, Hams; et al. (Nature Communications)
Migration frequently involves Rac-mediated protrusion of lamellipodia, formed by Arp2/3 complex-dependent branching thought to be crucial for force generation and stability of these networks. The formins FMNL2 and FMNL3 are Cdc42 effectors targeting to the lamellipodium tip and shown here to nucleate and elongate actin filaments with complementary activities in vitro. In migrating B16-F1 melanoma cells, both formins contribute to the velocity of lamellipodium protrusion. Loss of FMNL2/3 function in melanoma cells and fibroblasts reduces lamellipodial width, actin filament density and -bundling, without changing patterns of Arp2/3 complex incorporation. Strikingly, in melanoma cells, FMNL2/3 gene inactivation almost completely abolishes protrusion forces exerted by lamellipodia and modifies their ultrastructural organization. Consistently, CRISPR/Cas-mediated depletion of FMNL2/3 in fibroblasts reduces both migration and capability of cells to move against viscous media. Together, we conclude that force generation in lamellipodia strongly depends on FMNL formin activity, operating in addition to Arp2/3 complex-dependent filament branching.

Steady state EB cap size fluctuations are determined by stochastic microtubule growth and maturation - Rickman, Jamie; Düllberg, Christian F; Cade, Nicholas; Griffin, Lewis; Surrey, Thomas (PNAS)
Growing microtubules are protected from depolymerization by the presence of a GTP or GDP/Pi cap. End-binding proteins of the EB1 family bind to the stabilizing cap, allowing monitoring of its size in real time. The cap size has been shown to correlate with instantaneous microtubule stability. Here we have quantitatively characterized the properties of cap size fluctuations during steadystate growth and have developed a theory predicting their timescale and amplitude from the kinetics of microtubule growth and cap maturation. In contrast to growth speed fluctuations, cap size fluctuations show a characteristic timescale, which is defined by the lifetime of the cap sites. Growth fluctuations affect the amplitude of cap size fluctuations; however, cap size does not affect growth speed, indicating that microtubules are far from instability during most of their time of growth. Our theory provides the basis for a quantitative understanding of microtubule stability fluctuations during steady-state growth.

Hydrodynamic turbulence in quasi Keplerian rotating flows - Shi, Liang; Hof, Björn; Rampp, Markus; Avila, Marc (Physics of Fluids)
We report a direct-numerical-simulation study of the Taylor-Couette flow in the quasi-Keplerian regime at shear Reynolds numbers up to (105). Quasi-Keplerian rotating flow has been investigated for decades as a simplified model system to study the origin of turbulence in accretion disks that is not fully understood. The flow in this study is axially periodic and thus the experimental end-wall effects on the stability of the flow are avoided. Using optimal linear perturbations as initial conditions, our simulations find no sustained turbulence: the strong initial perturbations distort the velocity profile and trigger turbulence that eventually decays.

Safety verification of nonlinear hybrid systems based on invariant clusters - Kong, Hui; Bogomolov, Sergiy; Schilling, Christian; Jiang, Yu; Henzinger, Thomas A (Proceedings of the 20th International Conference on Hybrid Systems)
In this paper, we propose an approach to automatically compute invariant clusters for nonlinear semialgebraic hybrid systems. An invariant cluster for an ordinary differential equation (ODE) is a multivariate polynomial invariant g(u→, x→) = 0, parametric in u→, which can yield an infinite number of concrete invariants by assigning different values to u→ so that every trajectory of the system can be overapproximated precisely by the intersection of a group of concrete invariants. For semialgebraic systems, which involve ODEs with multivariate polynomial right-hand sides, given a template multivariate polynomial g(u→, x→), an invariant cluster can be obtained by first computing the remainder of the Lie derivative of g(u→, x→) divided by g(u→, x→) and then solving the system of polynomial equations obtained from the coefficients of the remainder. Based on invariant clusters and sum-of-squares (SOS) programming, we present a new method for the safety verification of hybrid systems. Experiments on nonlinear benchmark systems from biology and control theory show that our approach is efficient.